Gel electrolyte electrode, separator and lithium ion battery and their manufacturing method
Patent Information
- Application Number
- CN202410876760.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The existing gel electrolyte lithium-ion battery production process is complex, the electrolyte is unstable, it is difficult to fully wet the electrodes, and the preparation cost is high, which cannot meet the production requirements of high energy density batteries.
By using polymers with boron cross-linking structures, positive electrodes, negative electrodes, or membranes are prepared through the reaction of boric acid compounds with polymers containing active hydrogen functional groups, forming gel electrolytes. This reduces the complexity of the production process and improves the stability and wettability of the electrolyte.
It simplifies the production process, reduces the preparation cost, avoids the problems of electrolyte instability and difficulty in wetting, meets the needs of high energy density batteries, and improves the lithium-ion transference number and rate charge and discharge performance.
Smart Images

Figure CN118841633B_ABST
Abstract
Description
[0001] Related applications
[0002] This application claims priority to the earlier application filed in China on June 29, 2023, with application number 202310790546.0, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This invention relates to the field of lithium-ion batteries, specifically to a gel electrolyte electrode, a separator, and a lithium-ion battery, as well as methods for their fabrication. Background Technology
[0004] In lithium-ion batteries, using gel electrolytes instead of traditional liquid electrolytes has two advantages: First, it prevents electrolyte leakage, reduces the evaporation of electrolyte solvents, reduces solvent usage, and mitigates the risk of combustion and explosion, thereby improving safety performance; second, it reduces the contact between the electrolyte and the surface of active materials, thereby inhibiting electrolyte decomposition, extending battery life, and also contributing to improved safety performance.
[0005] The application of gel electrolytes in lithium-ion batteries mainly includes the following two methods. The first method involves adding a partially crystalline polymer to the electrolyte precursor to form a viscous liquid, which is then coated onto the electrode. The low-boiling-point solvent in the electrolyte precursor is then extracted, allowing the polymer and electrolyte to form a physically cross-linked gel. A representative polymer is the copolymer of vinylidene fluoride and hexafluoropropylene (VDF-co-HFP), commercialized by Sony. The second method involves adding monomers or oligomers containing multiple double-bond functional groups along with an initiator to the electrolyte. The electrolyte is then injected into the dry cell, and double-bond polymerization is initiated by heating or ultraviolet irradiation, transforming the electrolyte into a chemically cross-linked gel, also known as in-situ polymerization. Representative monomers or oligomers include various monomers or oligomers containing acrylate or methacrylate groups, commercialized by Samsung.
[0006] The first application method described above has very few polymer options; the only successful example is Sony's use of PVDF copolymers. However, this method has two major problems: first, the complex process leads to high costs; second, the gel electrolyte contains virtually no low-boiling-point solvents, resulting in low electrolyte conductivity and limiting the battery's rate and low-temperature performance. The second application method allows for a wider selection of monomers or oligomers, but it also has two major problems: first, the electrolyte is prone to gelation and can only be stored at low temperatures for short periods; second, electrolytes containing monomers or oligomers have high viscosity, making it difficult for the electrolyte to fully wet the pores in the electrode, which is incompatible with the low-porosity electrode requirements of high-energy-density batteries. Summary of the Invention
[0007] The problem this invention aims to solve is that the existing gel electrolyte lithium-ion battery production process is complex, the electrolyte is unstable, it is difficult to fully wet the electrodes, and the preparation cost is high, which cannot meet the production requirements of high energy density batteries.
[0008] To address the aforementioned problems, one objective of this invention is to provide a gel electrolyte lithium-ion battery comprising a polymer with a boron cross-linked structure and a method for preparing the same; another objective of this invention is to provide a gel electrolyte electrode comprising a polymer with a boron cross-linked structure and a method for preparing the same; and a third objective of this invention is to provide a separator comprising a polymer with a boron cross-linked structure and a method for preparing the same.
[0009] To solve the above problems, the technical solution of the present invention is as follows:
[0010] In a first aspect, in one specific embodiment of the present invention, the present invention provides a gel electrolyte lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, the negative electrode, or the separator comprises a polymer having a boron crosslinking structure, wherein the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3, and 4.
[0011]
[0012] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or alkyl.
[0013] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; preferably, the boric acid compound includes one or more of boric acid, phenylboronic acid, phenyldiboronic acid, 1,3,5-phenyltriboronic acid, alkylboronic acid, naphthaleneboronic acid, and heteroarylboronic acid.
[0014] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; preferably, the boric acid compound includes one or more of boric acid, phenylboronic acid and alkylboronic acid.
[0015] Preferably, the polymer containing active hydrogen functional groups includes one or more of the following: polymers containing hydroxyl groups, polymers containing carboxyl groups, polymers containing sulfonic acid groups, polymers containing sulfuric acid groups, polymers containing phosphate groups, polymers containing amine groups, and polymers containing substituted amine groups.
[0016] In some embodiments of the present invention, the polymer containing active hydrogen functional groups includes one or more of polyolefins containing active hydrogen functional groups, polyethers containing active hydrogen functional groups, polyesters containing active hydrogen functional groups, polyamides containing active hydrogen functional groups, and polycarbonates containing active hydrogen functional groups.
[0017] The polymers containing active hydrogen functional groups include one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates.
[0018] In some embodiments of the present invention, at 25-60°C, the polymer with boron cross-linked structure has a swelling degree greater than 50% in the electrolyte, preferably 50-10000%; preferably, the swelling loss rate of the polymer with boron cross-linked structure in the electrolyte is <5%.
[0019] In some embodiments of the present invention, the positive electrode includes a current collector and a positive electrode coating material coated on the current collector; preferably, the positive electrode coating material includes a positive electrode active material and a polymer having a boron crosslinking structure;
[0020] And / or, the negative electrode includes a current collector and a negative electrode coating material coated on the current collector; preferably, the negative electrode coating material includes a negative electrode active material and a polymer having a boron crosslinking structure;
[0021] And / or, the diaphragm comprises a polymer porous membrane and a diaphragm coating material coated on the polymer porous membrane; preferably, the diaphragm coating material comprises inorganic particles and a polymer having a boron crosslinking structure.
[0022] In some embodiments of the present invention, the electrolyte comprises an organic solvent and a lithium salt; preferably, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate.
[0023] More preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(fluorosulfonyl)imide, preferably lithium hexafluorophosphate.
[0024] The electrolyte also includes one or more of the following: unsaturated cyclic carbonates, fluorocyclic carbonates, cyclic sulfonates, and cyclic sulfates.
[0025] Preferably, the unsaturated cyclic carbonate is selected from vinylene carbonate and / or vinyl ethylene carbonate;
[0026] And / or, the fluorocyclic carbonate is selected from at least one of fluoroethylene carbonate, trifluoromethyl ethylene carbonate or difluoroethylene carbonate;
[0027] And / or, the cyclic sulfonyl lactone is selected from at least one of 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone and propenyl-1,3-sulfonyl lactone;
[0028] And / or, the cyclic sulfate ester is selected from at least one of vinyl sulfate, propylene sulfate, and 4-methylvinyl sulfate.
[0029] In a second aspect, the present invention provides a method for preparing the above-mentioned gel electrolyte lithium-ion battery, comprising the following steps: forming a cell by a positive electrode, a negative electrode and a separator and placing it in a battery casing, then injecting an electrolyte to obtain a semi-finished lithium-ion battery; forming and venting the semi-finished lithium-ion battery and then sealing the electrolyte injection port of the battery casing to obtain a gel electrolyte lithium-ion battery.
[0030] Wherein, at least one of the positive electrode, negative electrode, or separator is prepared according to the following method:
[0031] (1) The positive electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a positive electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the positive electrode;
[0032] (2) The negative electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a negative electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the negative electrode;
[0033] (3) The diaphragm is prepared by the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with diaphragm slurry, then coating the slurry onto a polymer porous membrane, and then drying to obtain the diaphragm;
[0034] Preferably, the drying temperature is 60-120℃;
[0035] More preferably, based on the total weight of the positive electrode slurry (100%), the weight percentage of the sum of the boric acid compound and the polymer containing active hydrogen functional groups is 1-10%; and / or,
[0036] Based on the total weight of the negative electrode slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-10%; and / or,
[0037] Based on the total weight of the diaphragm slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-50%.
[0038] Thirdly, in one specific embodiment of the present invention, the present invention also provides an electrode for a lithium-ion battery, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3 and 4.
[0039]
[0040] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group;
[0041] Preferably, the electrode is a positive electrode or a negative electrode.
[0042] Fourthly, the present invention also provides a method for preparing the electrode of the above-mentioned lithium-ion battery, comprising the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with an electrode slurry, and then coating and drying to obtain the lithium-ion battery electrode;
[0043] Preferably, the drying temperature is 60-120℃;
[0044] More preferably, the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-10% based on the total weight of the electrode paste (100%).
[0045] Fifthly, in one specific embodiment of the present invention, the present invention also provides a separator for a lithium-ion battery, comprising a polymer porous membrane and a separator coating material coated on the polymer porous membrane, wherein the separator coating material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below.
[0046]
[0047] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group;
[0048] Preferably, the polymer porous membrane is a polyolefin microporous membrane or a nonwoven fabric.
[0049] In a sixth aspect, the present invention also provides a method for preparing the separator of the above-mentioned lithium-ion battery, comprising the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a separator slurry, coating and drying to obtain the separator of the lithium-ion battery.
[0050] Preferably, the drying temperature is 60-120℃;
[0051] Based on the total weight of the diaphragm slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-50%.
[0052] In another embodiment of the present invention, the present invention provides the following specific technical solution:
[0053] In one specific embodiment of the present invention, a gel electrolyte lithium-ion battery is provided, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, negative electrode, or separator comprises a polymer with a boron crosslinking structure, wherein the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3, and 4.
[0054]
[0055] R1 is selected from hydroxyl, alkyl, aryl or heteroaryl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0056] In some embodiments of the present invention, the above-mentioned gel electrolyte lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, negative electrode, or separator comprises a polymer with a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3, and 4.
[0057]
[0058] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or alkyl.
[0059] In some embodiments of the present invention, a positive electrode, a negative electrode, a separator, and an electrolyte are included, wherein when X1, X2, and X3 are each independently selected from O, the groups containing O are selected from:
[0060]
[0061] When X1, X2, and X3 are each independently selected from NR2, the group containing NR2 is selected from...
[0062] Wherein, when the O-containing group is selected from At this time, O is directly connected to B, and C is directly connected to the polymer chain;
[0063] When the O-containing group is selected from At this time, O is directly connected to B, and S is directly connected to the polymer chain;
[0064] When the group containing NR2 is selected from At this time, N is directly connected to B, and C is directly connected to the polymer chain.
[0065] In one specific embodiment of the present invention, a gel electrolyte lithium-ion battery is provided, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas: Formula 1, Formula 2, Formula 3, Formula 4, Formula 5, Formula 6, Formula 7, and Formula 8.
[0066]
[0067] R1 is selected from one of hydroxyl, alkyl, phenyl, naphthalene or heteroaryl, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0068] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group;
[0069] Preferably, the boric acid compound includes one or more of boric acid, phenylboronic acid, phenyldiboronic acid, 1,3,5-phenyltriboronic acid, alkylboronic acid, naphthaleneboronic acid, and heteroarylboronic acid; preferably, the polymer containing an active hydrogen functional group includes one or more of polymers containing hydroxyl groups, polymers containing carboxyl groups, polymers containing sulfonic acid groups, polymers containing sulfuric acid groups, polymers containing phosphate groups, polymers containing amine groups, and polymers containing substituted amine groups.
[0070] In some embodiments of the present invention, the boric acid compound includes one or more of boric acid, phenylboronic acid and alkylboronic acid.
[0071] In some embodiments of the present invention, the polymer containing active hydrogen functional groups includes one or more of polyolefins containing active hydrogen functional groups, polyethers containing active hydrogen functional groups, polyesters containing active hydrogen functional groups, polyamides containing active hydrogen functional groups, and polycarbonates containing active hydrogen functional groups.
[0072] In some embodiments of the present invention, at 25-60°C, the polymer with boron cross-linked structure has a swelling degree greater than 50% in the electrolyte, preferably 50-10000%; preferably, the swelling loss rate of the polymer with boron cross-linked structure in the electrolyte is <5%.
[0073] In some embodiments of the present invention, the positive electrode includes a current collector and a positive electrode coating material coated on the current collector; preferably, the positive electrode coating material includes a positive electrode active material and the polymer having a boron crosslinking structure;
[0074] And / or, the negative electrode includes a current collector and a negative electrode coating material coated on the current collector; preferably, the negative electrode coating material includes a negative electrode active material and the polymer having a boron crosslinking structure;
[0075] And / or, the diaphragm comprises a polymer porous membrane and a diaphragm coating material coated on the polymer porous membrane; preferably, the diaphragm coating material comprises inorganic particles and a polymer having a boron crosslinking structure.
[0076] In some embodiments of the present invention, the electrolyte comprises an organic solvent and a lithium salt; preferably, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate.
[0077] More preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(fluorosulfonyl)imide, preferably lithium hexafluorophosphate.
[0078] In some embodiments of the present invention, the electrolyte further includes one or more of unsaturated cyclic carbonates, fluorocyclic carbonates, cyclic sulfonates and cyclic sulfates.
[0079] Preferably, the unsaturated cyclic carbonate is selected from vinylene carbonate and / or vinyl ethylene carbonate.
[0080] And / or the fluorocyclic carbonate is selected from at least one of fluoroethylene carbonate, trifluoromethyl ethylene carbonate, or difluoroethylene carbonate.
[0081] And / or the cyclic sulfonyl lactone is selected from at least one of 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, and propenyl-1,3-sulfonyl lactone.
[0082] And / or the cyclic sulfate ester is selected from at least one of vinyl sulfate, propylene sulfate, and 4-methylvinyl sulfate.
[0083] On the other hand, the present invention also provides a method for preparing the above-mentioned gel electrolyte lithium-ion battery, comprising the following steps: forming a cell by a positive electrode, a negative electrode and a separator and placing it in a battery casing, then injecting an electrolyte to obtain a semi-finished lithium-ion battery; forming and venting the semi-finished lithium-ion battery and then sealing the liquid injection port of the battery casing to obtain a gel electrolyte lithium-ion battery.
[0084] Wherein, at least one of the positive electrode, negative electrode, or separator is prepared according to the following method:
[0085] (1) The positive electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a positive electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the positive electrode;
[0086] (2) The negative electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a negative electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the negative electrode;
[0087] (3) The diaphragm is prepared by the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with diaphragm slurry, then coating the slurry onto a polymer porous membrane, and then drying to obtain the diaphragm;
[0088] Preferably, the drying temperature is 60-120℃;
[0089] More preferably, based on the total weight of the positive electrode slurry (100%), the weight percentage of the sum of the boric acid compound and the polymer containing active hydrogen functional groups is 1-10%; and / or,
[0090] Based on the total weight of the negative electrode slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-10%; and / or,
[0091] Based on the total weight of the diaphragm slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-50%.
[0092] On the other hand, the present invention also provides an electrode for a lithium-ion battery, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below.
[0093]
[0094] R1 is selected from hydroxyl, alkyl, aryl or heteroaryl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0095] In some embodiments of the present invention, the present invention also provides an electrode for a lithium-ion battery, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below.
[0096]
[0097] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group;
[0098] Preferably, the electrode is a positive electrode or a negative electrode.
[0099] In some embodiments of the present invention, when X1, X2, and X3 are each independently selected from O, the groups containing O are selected from:
[0100]
[0101] When X1, X2, and X3 are each independently selected from NR2, the group containing NR2 is selected from...
[0102] Wherein, when the O-containing group is selected from At this time, O is directly connected to B, and C is directly connected to the polymer chain;
[0103] When the O-containing group is selected from At this time, O is directly connected to B, and S is directly connected to the polymer chain;
[0104] When the group containing NR2 is selected from At this time, N is directly connected to B, and C is directly connected to the polymer chain.
[0105] In some embodiments of the present invention, the present invention also provides an electrode for a lithium-ion battery, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3, 4, 5, 6, 7 and 8.
[0106]
[0107] R1 is selected from one of hydroxyl, alkyl, phenyl, naphthalene or heteroaryl, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0108] On the other hand, the present invention also provides a method for preparing the electrode of the above-mentioned lithium-ion battery, comprising the following steps: mixing boric acid compound and polymer containing active hydrogen functional groups with electrode slurry, and then coating and drying to obtain the lithium-ion battery electrode;
[0109] Preferably, the drying temperature is 60-120℃;
[0110] More preferably, the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-10% based on the total weight of the electrode paste (100%).
[0111] On the other hand, the present invention also provides a separator for a lithium-ion battery, comprising a polymer porous membrane and a separator coating material coated on the polymer porous membrane, wherein the separator coating material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3 and 4.
[0112]
[0113] R1 is selected from one of hydroxyl, alkyl, aryl or heteroaryl groups, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0114] In some embodiments of the present invention, the separator of the lithium-ion battery described above comprises a polymer porous membrane and a separator coating material coated on the polymer porous membrane, wherein the separator coating material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below.
[0115]
[0116] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group;
[0117] Preferably, the polymer porous membrane is a polyolefin microporous membrane or a nonwoven fabric.
[0118] In some embodiments of the present invention, in the separator of the lithium-ion battery described above, when X1, X2, and X3 are each independently selected from O, the groups containing O are selected from:
[0119]
[0120] When X1, X2, and X3 are each independently selected from NR2, the group containing NR2 is selected from...
[0121] Wherein, when the O-containing group is selected from At this time, O is directly connected to B, and C is directly connected to the polymer chain;
[0122] When the O-containing group is selected from At this time, O is directly connected to B, and S is directly connected to the polymer chain;
[0123] When the group containing NR2 is selected from At this time, N is directly connected to B, and C is directly connected to the polymer chain.
[0124] In some embodiments of the present invention, the present invention also provides a separator for a lithium-ion battery, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3, 4, 5, 6, 7 and 8.
[0125]
[0126] R1 is selected from one of hydroxyl, alkyl, phenyl, naphthalene or heteroaryl, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0127] On the other hand, the present invention also provides a method for preparing the separator of the above-mentioned lithium-ion battery, comprising the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with separator slurry, coating and drying to obtain the separator of the lithium-ion battery.
[0128] Preferably, the drying temperature is 60-120℃;
[0129] Based on the total weight of the diaphragm slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-50%.
[0130] Compared with the prior art, the present invention has the following beneficial effects:
[0131] (1) At least one of the positive electrode, negative electrode or separator of the lithium-ion battery of the present invention contains a polymer with a boron cross-linking structure. After the polymer with the boron cross-linking structure comes into contact with the electrolyte, it can absorb the electrolyte and swell to form a gel electrolyte. It can use the traditional production process of lithium-ion batteries, reduce the complexity of the preparation process, reduce the production equipment cost, and avoid the problem of electrolyte instability and difficulty in wetting the electrode caused by directly adding the gel polymer precursor to the electrolyte in the prior art. It can meet the needs of high energy density batteries.
[0132] (2) The polymer with boron cross-linking structure can ensure that the polymer will not dissolve in the electrolyte. By selecting a suitable polymer chain, the polymer can absorb the electrolyte well and swell to form a gel electrolyte, thereby preventing electrolyte leakage and reducing the contact between the electrolyte and the surface of the active material, thus reducing the decomposition and consumption of the electrolyte.
[0133] (3) Polymers with boron cross-linking structure have Lewis acid properties and can complex with anions in the electrolyte, thereby reducing the migration of anions under the action of an electric field, increasing the lithium ion transference number, and improving the rate charge and discharge performance of gel electrolyte lithium-ion batteries. Detailed Implementation
[0134] To make the objectives, technical solutions, and technical effects of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. The embodiments described below are some embodiments of the present invention, but not all embodiments. In conjunction with the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0135] In this specification, the designation of groups (atomic groups) includes both unsubstituted and substituted groups unless otherwise specified. For example, "alkyl" includes not only unsubstituted alkyl groups (unsubstituted alkyl groups) but also substituted alkyl groups (substituted alkyl groups).
[0136] To better understand the above technical solution, the present invention will be further described in detail below.
[0137] In a first aspect, in one specific embodiment of the present invention, the present invention provides a gel electrolyte lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, the negative electrode, or the separator comprises a polymer having a boron crosslinking structure, wherein the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3, 4, 5, 6, 7, and 8.
[0138]
[0139]
[0140] Wherein, R1 is selected from one of hydroxyl, alkyl, phenyl, naphthalene, or heteroaryl groups, and X1, X2, and X3 are each independently selected from one of the following groups.
[0141]
[0142] Wherein, R2 is a hydrogen atom or an alkyl group;
[0143] Among them, when X1, X2, and X3 are each independently selected At this time, O is directly connected to B, and C is directly connected to the polymer chain;
[0144] When X1, X2, and X3 are each independently selected At this time, O is directly connected to B, and S is directly connected to the polymer chain;
[0145] When X1, X2, and X3 are each independently selected At this time, N is directly connected to B, and C is directly connected to the polymer chain.
[0146] In some specific embodiments of the present invention, the heteroaryl group is selected from pyridyl, thiophenyl, pyrroleyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl.
[0147] In some specific embodiments of the present invention, the alkyl, phenyl, naphthyl, or heteroaryl group may be substituted with one or more substituents. Each substituent is independently selected from C1-6 alkyl, C1-6 haloalkyl, halogen, C1-6 alkoxy, carbonyl, benzyloxy, cyano, or ester groups.
[0148] In some specific embodiments of the present invention, each of the substituents is independently selected from C1-4 alkyl, C1-4 haloalkyl, halogen, C1-4 alkoxy, carbonyl, benzyloxy, cyano or ester.
[0149] In some specific embodiments of the present invention, each of the substituents is independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl, bromoethyl, fluoroethyl, chloroethyl, 1,1-difluoroethyl, 1,1-dichloroethyl, fluoropropyl, chloropropyl, trifluoromethyl, 1,1-difluoropropyl, 1,1,1-trifluoropropyl, fluorobutyl, chlorobutyl, 1,1-difluorobutyl The following groups are listed: methyl, fluorinated, chloromeric, bromine, iodomethyl, methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, tert-butoxy, methyl ketone, formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, benzyloxy, cyano, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, tert-butyl ester, phenyl acetate, or dibutyl phthalate.
[0150] In some specific embodiments of the present invention, R1 is selected from hydroxyl, alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl; the alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl may be substituted by one or more substituents; each substituent is independently selected from C1-6 alkyl, C1-6 haloalkyl, halogen, C1-6 alkoxy, carbonyl, benzyloxy, cyano, or ester.
[0151] In some specific embodiments of the present invention, R1 is selected from hydroxyl, alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrolyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl; the alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrolyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl may be substituted by one or more substituents; each substituent is independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl, bromoethyl, fluoroethyl, chloroethyl, and 1,1-difluoroethyl. 1,1-Dichloroethyl, fluoropropyl, chloropropyl, 1,1-difluoropropyl, 1,1,1-trifluoropropyl, fluorobutyl, chlorobutyl, 1,1-difluorobutyl, fluoro, chloro, bromo, iodo, methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, tert-butoxy, methyl ketone, formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, benzyloxy, cyano, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, tert-butyl acetate, phenyl acetate, or dibutyl phthalate.
[0152] In some specific embodiments of the present invention, R1 is selected from hydroxyl, C1-6 alkyl, phenyl, halogen-substituted phenyl, alkyl-substituted phenyl, haloalkyl-substituted phenyl, cyano-substituted phenyl, carbonyl-substituted phenyl, alkoxy-substituted phenyl, naphthyl, pyridyl, thiophenyl, halogen-substituted thiophenyl, carbonyl-substituted thiophenyl, pyrroleyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, halogen-substituted pyrimidinyl, furanyl, indoleyl, or ester-substituted indoleyl.
[0153] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, fluorinated phenyl, chlorosubstituted phenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, butylphenyl, isobutylphenyl, tert-butylphenyl, chlorobenzyl, bromophenylethyl, fluoromethyl substituted phenyl, difluoromethyl substituted phenyl, trifluoromethyl substituted phenyl, chloromethyl substituted phenyl, bromomethyl substituted phenyl, bromoethyl substituted phenyl, cyano substituted phenyl, aldehyde substituted phenyl, methoxy substituted phenyl, ethoxy substituted phenyl, propoxy substituted phenyl, butoxy substituted phenyl, naphthyl, pyridyl, thiophenyl, fluorinated thiophenyl, chlorosubstituted thiophenyl, methyl ketone substituted thiophenyl, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, fluorinated pyrimidinyl, bromosubstituted pyrimidinyl, furanyl, indole, or tert-butyl ester substituted indole.
[0154] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, etc.
[0155] It should be noted that the dashed line in the above selection of R1 group represents a direct connection with B.
[0156] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of the following groups.
[0157]
[0158] R2 is a hydrogen atom or a C1-6 alkyl group.
[0159] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of the following groups.
[0160]
[0161] R2 can be a hydrogen atom, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, tert-hexyl, or tert-hexyl.
[0162] It should be noted that the wavy lines in Equations 1-6 described in this article represent polymer chains.
[0163] In some embodiments of the present invention, the polymer chain is selected from one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates.
[0164] In one specific embodiment of the present invention, a gel electrolyte lithium-ion battery is provided, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, negative electrode, or separator comprises a polymer having a boron crosslinking structure, wherein the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3, and 4.
[0165]
[0166] R1 is selected from hydroxyl, alkyl, and phenyl, and X1, X2, and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group.
[0167] The alkyl or phenyl group may be substituted with one or more substituents. The selection of the substituents is the same as that of the alkyl, phenyl, naphthyl, or heteroaryl groups mentioned above.
[0168] In some specific embodiments of the present invention, R1 is selected from hydroxyl, C1-6 alkyl, phenyl, halogen-substituted phenyl, alkyl-substituted phenyl, haloalkyl-substituted phenyl, cyano-substituted phenyl, carbonyl-substituted phenyl, or alkoxy-substituted phenyl.
[0169] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, fluorinated phenyl, chlorosubstituted phenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, butylphenyl, isobutylphenyl, tert-butylphenyl, chlorobenzyl, bromophenylethyl, fluoromethyl substituted phenyl, difluoromethyl substituted phenyl, trifluoromethyl substituted phenyl, chloromethyl substituted phenyl, bromomethyl substituted phenyl, bromoethyl substituted phenyl, cyano substituted phenyl, aldehyde substituted phenyl, methoxy substituted phenyl, ethoxy substituted phenyl, propoxy substituted phenyl, or butoxy substituted phenyl.
[0170] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or a C1-6 alkyl group.
[0171] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, tert-hexyl, or tert-hexyl.
[0172] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group, wherein the boric acid compound includes one or more of boric acid, phenylboronic acid, phenyldiboronic acid, 1,3,5-phenyltriboronic acid, alkylboronic acid, naphthaleneboronic acid, and heteroarylboronic acid.
[0173] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; wherein the boric acid compound includes one or more of boric acid, phenylboronic acid and alkylboronic acid.
[0174] The heteroaryl group in the heteroarylboronic acid is selected from pyridyl, pyrazinyl, pyrimidinyl, furanyl, pyrroleyl, thiophenyl, thiazolyl, or oxazolyl.
[0175] The phenyl, alkyl, naphthyl, and heteroaryl groups in the phenylboronic acid, alkylboronic acid, naphthylboronic acid, and heteroarylboronic acid can be replaced by one or more substituents. The selection of the substituents is the same as the selection of the alkyl, phenyl, naphthyl, or heteroaryl substituents mentioned above.
[0176] Preferably, phenylboronic acid includes, but is not limited to, 5-chloro-2-methoxyphenylboronic acid, 4-cyanophenylboronic acid, 5-aldehyde-2-methoxyphenylboronic acid, 4-isopropylphenylboronic acid, 2-chloro-4-methylphenylboronic acid, 3-chloro-5-trifluoromethylphenylboronic acid, or 4-benzyloxy-3-methoxyphenylboronic acid; preferably, phenyldiboronic acid includes, but is not limited to, 1,3-phenyldiboronic acid and / or 1,4-phenyldiboronic acid; preferably, alkylboronic acid includes, but is not limited to, methylboronic acid, ethylboronic acid, propylboronic acid, isopropylboronic acid, n-butylboronic acid, isobutylboronic acid, and tert-butylboronic acid. Or fluoromethylboronic acid; preferably, naphthaleneboronic acid includes, but is not limited to, 1-naphthaleneboronic acid, 2-naphthaleneboronic acid, 1,5-dinaphthaleneboronic acid or 2,6-dinaphthaleneboronic acid; preferably, heteroarylboronic acid includes, but is not limited to, 3-pyridineboronic acid, 2-fluoro-3-pyridineboronic acid, 2-bromopyridine-4-boronic acid, 2-thiopheneboronic acid, (4-fluorothiophene-2-yl)boronic acid, 5-acetyl-2-thiopheneboronic acid, 2-chlorothiophene-3-boronic acid, 2-furanboronic acid, 2-pyrroloboronic acid, 3-quinolineboronic acid, 2-imidazoliumboronic acid or N-(BOC)-7-fluoroindole-2-boronic acid.
[0177] Preferably, the polymer containing active hydrogen functional groups includes one or more of the following: polymers containing hydroxyl groups, polymers containing carboxyl groups, polymers containing sulfonic acid groups, polymers containing sulfate groups, polymers containing phosphate groups, polymers containing amine groups, and polymers containing substituted amine groups.
[0178] Specifically, this invention involves mixing boric acid compounds and polymers containing active hydrogen functional groups with electrode slurry or diaphragm slurry, followed by coating and drying to obtain electrodes or diaphragms containing polymers with boron cross-linked structures. After coating, the boric acid compounds and polymers containing active hydrogen functional groups undergo a dehydration reaction during high-temperature baking. An example of this reaction is shown below:
[0179]
[0180]
[0181]
[0182] R2 is a hydrogen atom or an alkyl group.
[0183] It should be noted that the wavy lines in the molecular formula described in this article represent polymer chains.
[0184] In some embodiments of the present invention, the polymer chain is selected from one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates.
[0185] In some embodiments of the present invention, the polymer containing an active hydrogen functional group is selected from one or more of polyolefins containing active hydrogen functional groups, polyethers containing active hydrogen functional groups, polyesters containing active hydrogen functional groups, polyamides containing active hydrogen functional groups, and polycarbonates containing active hydrogen functional groups. The polymers containing active hydrogen functional groups include one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates. Polyolefins, polyethers, polyesters, polyamides, and polycarbonates containing active hydrogen functional groups are classified according to their main chain structures. For example, the structural formulas of polyolefins containing active hydrogen functional groups are shown in Formula 24; the structural formulas of polyethers containing active hydrogen functional groups are shown in Formula 25 or 26; the structural formulas of polyesters containing active hydrogen functional groups are shown in Formula 27, 28, 29, or 30; the structural formulas of polycarbonates containing active hydrogen functional groups are shown in Formula 31 or 32; and the structural formulas of polyamides containing active hydrogen functional groups are shown in Formula 33 or 34.
[0186]
[0187] R3, R4, and R5 are each independently selected from hydrocarbon groups or substituted hydrocarbon groups containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, or halogen. R6 is selected from alkylene groups or substituted alkylene groups containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, or halogen. X is selected from -OH and -NHR2 (where R2 is a hydrogen atom or an alkyl group). m and l are integers greater than or equal to 1, and n is an integer greater than or equal to 2.
[0188]
[0189] Where R is the part of a small molecule polyol or oligomeric polyol after removing the hydroxyl group, R7 is a alkylene group or a substituted alkylene group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, and halogen, R8 is a alkylene group or a substituted alkylene group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, and halogen, X is selected from -OH and -NHR2 (where R2 is a hydrogen atom or alkyl group), m and l are integers greater than or equal to 1, and n is an integer greater than or equal to 2.
[0190]
[0191] Where R is the fraction of a small molecule polyol or oligomeric polyol after removing the hydroxyl group, R9, R 11 ,R 12 It is a substituted alkyl group or a substituted alkyl group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, or halogen, R 10 ,R 13 ,R 14It is a substituted alkyl group or a substituted alkyl group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, and halogen. X is selected from -OH and -NHR2 (where R2 is a hydrogen atom or an alkyl group), Y1 and Y2 are selected from -H, -OH, and -NHR2 and at least one of them is not -H (where R2 is a hydrogen atom or an alkyl group), m and l are integers greater than or equal to 1, and n is an integer greater than or equal to 2.
[0192]
[0193] Where R is the portion of a small molecule polyol or oligomeric polyol after removing the hydroxyl group, R 15 It is a substituted alkyl group or a substituted alkyl group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, or halogen, R 16 It is a substituted alkyl group or a substituted alkyl group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, and halogen. X is selected from -OH and -NHR2 (where R2 is a hydrogen atom or an alkyl group), m and l are integers greater than or equal to 1, and n is an integer greater than or equal to 2.
[0194]
[0195] Where R 17 ,R 18 ,R 19 It is a substituted alkyl group or a substituted alkyl group containing one or more elements such as oxygen, nitrogen, sulfur, phosphorus, or halogen, where n is an integer greater than or equal to 2.
[0196] The synthetic route for polyolefins containing active hydrogen functional groups involves the free radical polymerization of monomers containing double bonds under the action of an initiator. Common monomers containing double bonds include acrylonitrile, acrylates, methacrylates, cyanoacrylates, N-vinylpyrrolidone, vinylpyridine, N,N-dimethylacrylamide, etc. In addition, in order to introduce functional groups containing active hydrogen into the polymer chain, it is also necessary to introduce monomers containing both active hydrogen and double bonds to copolymerize with the above-mentioned common monomers containing double bonds. Monomers containing both active hydrogen and double bonds include acrylic acid, acrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, ethylene glycol monovinyl ether, vinyl sulfonic acid, allyl sulfonic acid, styrene sulfonic acid, 2-hydroxyethyl methacrylate phosphate, etc.
[0197] The synthetic route for polyethers containing active hydrogen functional groups involves the ring-opening polymerization of epoxy monomers initiated by polyols to obtain polyether polyols. Representative polyols include ethylene glycol, glycerol, trimethylolpropane, pentaerythritol, etc., and representative epoxy monomers include ethylene oxide, propylene oxide, 1,3-dioxolane, glycidyl ether, epichlorohydrin, etc.
[0198] The synthetic routes for polyesters containing active hydrogen functional groups fall into two categories. One category involves the ring-opening polymerization of lactone monomers initiated by initiators containing polyols, polycarboxylic acids, or hydroxycarboxylic acids. These routes involve using polyols, polycarboxylic acids, or compounds containing hydroxycarboxylic acids as initiators to induce the ring-opening polymerization of lactone monomers, yielding polyester polyols, polyester polyacids, or polyesters containing multiple hydroxyl and carboxylic acids. Representative polyols include ethylene glycol, glycerol, trimethylolpropane, pentaerythritol, and inositol. Representative polycarboxylic acids include succinic acid, trimalonic acid, and trimesodium pyromellitic acid. One type of polyol is obtained by polycondensation of diacid monomers and diol monomers. Representative initiators containing hydroxycarboxylic acids include glycolic acid, malic acid, citric acid, and tartaric acid. Representative lactone monomers include glycolide, lactide, δ-valerol, and ε-caprolactone. Another type of polyol is obtained by polycondensation of diacid monomers and diol monomers. Its synthetic route is to obtain polyester polyols by polycondensation of diacid monomers and diol monomers. Representative diacids include succinic acid, adipic acid, and terephthalic acid. Representative diols include ethylene glycol, 1,3-propanediol, and 1,6-hexanediol.
[0199] The synthetic route of polycarbonate containing active hydrogen functional groups is to obtain polycarbonate polyols by ring-opening polymerization of cyclic carbonate monomers initiated by polyols. Representative polyols include ethylene glycol, glycerol, trimethylolpropane, pentaerythritol, etc., and representative cyclic carbonate monomers include ethylene carbonate, propylene carbonate, etc.
[0200] The synthetic routes for polyamides containing active hydrogen functional groups fall into two categories. One type involves the ring-opening polymerization of caprolactam monomers initiated by alkali metals or water to obtain polyamides with amino and carboxylate groups at both ends, respectively. Representative alkali metal initiators include sodium hydroxide and sodium methoxide. The other type involves the polycondensation reaction of diacid monomers and diamine monomers to obtain polyamides. Representative diacids include succinic acid, adipic acid, and terephthalic acid, while representative diamines include ethylenediamine, hexamethylenediamine, polyetheramine, and p-phenylenediamine.
[0201] It should be noted that the electrode slurry described in this invention refers to a fluid formed by mixing and uniformly dispersing electrode active materials, conductive agents, binders, and other materials in a solvent. The diaphragm slurry refers to a fluid formed by mixing and dispersing inorganic particles, binders, and other materials in a solvent.
[0202] In some embodiments of the present invention, the polymer containing active hydrogen functional groups includes, but is not limited to, one or more of the following polymers:
[0203]
[0204]
[0205] Oligomer 11 (polyethylene glycol PEG400), oligomer 12 (polyethylene glycol PEG1000), oligomer 13 (polypropylene glycol PPG2000) and oligomer 14 (polypropylene glycol PPG4000).
[0206] In some embodiments of the present invention, the polymer having a boron crosslinking structure in the positive electrode is obtained by reacting one or more of oligomers 1, 3, 4, 5, 6, 7 or 14 with a boric acid compound; preferably, based on the total weight of the positive electrode slurry as 100%, the weight percentage of the sum of the weights of the polymer containing active hydrogen functional groups and the boric acid compound is 1-10%, preferably 2-7%.
[0207] In some embodiments of the present invention, based on the total weight of the positive electrode slurry as 100%, the weight percentage of the sum of the weights of the polymer containing active hydrogen functional groups and the boric acid compound can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within a range defined by any two of the above specific values as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other range.
[0208] In some embodiments of the present invention, the polymer with a boron cross-linked structure in the negative electrode is obtained by reacting one or more of oligomers 8, 9, 11, 12, or 13 with a boric acid compound. Preferably, based on 100% of the total weight of the negative electrode slurry, the weight percentage of the polymer containing active hydrogen functional groups and the boric acid compound is 1-10%, more preferably 2-9%.
[0209] In some embodiments of the present invention, based on the total weight of the negative electrode slurry as 100%, the weight percentage of the sum of the weights of the polymer containing active hydrogen functional groups and the boric acid compound can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within a range defined by any two of the above specific values as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other range.
[0210] In some embodiments of the present invention, the polymer having a boron crosslinking structure in the diaphragm is obtained by reacting one or more of oligomers 8, 9, 10, or 11 with a boric acid compound. Preferably, based on 100% of the total weight of the diaphragm slurry, the weight percentage of the polymer containing active hydrogen functional groups and the boric acid compound is 1-50%, more preferably 5-15%, and more preferably 5-12%.
[0211] In some embodiments of the present invention, based on the total weight of the positive electrode slurry as 100%, the weight percentage of the sum of the weights of the polymer containing active hydrogen functional groups and the boric acid compound can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or within a numerical range defined by any two of the above specific values as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other range.
[0212] In some embodiments of the present invention, the molar ratio of the polymer containing active hydrogen functional groups to the boric acid compound is 0.1-50:1, preferably 0.1-20:1, and more preferably 0.1-2:1.
[0213] In some embodiments of the present invention, at a temperature of 25-60°C, the polymer having a boron crosslinked structure has a swelling degree greater than 50% in the electrolyte, preferably a swelling loss rate of <5%, more preferably a swelling degree of 50-10000%, further preferably a swelling degree of 100% to 5000%, and even more preferably a swelling degree of [missing information - likely a value].
[0214] 100%–1000%. When the swelling degree is less than 50%, the conductivity of the gel electrolyte formed by the polymer with boron cross-linking structure is very low, the internal resistance of the battery increases, thus affecting the charge-discharge rate performance and low-temperature cycle performance of the battery; when the swelling degree is greater than 10000%, the mechanical properties of the above-mentioned polymer with boron cross-linking structure deteriorate, and it may even dissolve in the electrolyte, losing its function as a gel electrolyte.
[0215] It should be noted that the swelling degree mentioned in this invention refers to the ratio of the mass difference of the polymer with boron cross-linking structure before and after immersion in the electrolyte to the mass of the polymer before immersion. The specific test method is as follows: A circular film with a thickness of 30 μm and a size of 16 mm * 16 mm is made from the polymer with boron cross-linking structure. The mass of the film is weighed, and the film is immersed in 10 g of electrolyte. After sealing, it is stored at 60°C. Every 8 hours, the film is removed, the electrolyte on the surface is wiped off, the thickness is measured, and the film is weighed. It is then returned to the electrolyte, sealed, and stored at 60°C until the film thickness and mass remain unchanged in three consecutive tests. At this point, the polymer film with boron cross-linking structure is considered to have reached a swelling equilibrium state. The swelling degree is calculated according to the following formula:
[0216]
[0217] In the above formula, m0 represents the mass of the polymer membrane with boron cross-linking structure before immersion in the electrolyte, and m1 represents the mass of the polymer membrane with boron cross-linking structure after immersion in the electrolyte and reaching swelling equilibrium.
[0218] The swelling loss rate described in this invention refers to the ratio of the mass loss due to partial dissolution of a boron-crosslinked polymer in an electrolyte to the mass of the polymer before swelling. The specific testing method is as follows: A circular film with a thickness of 30 μm and a size of 16 mm * 16 mm is prepared from the boron-crosslinked polymer. The mass of the film is weighed, and the film is immersed in 10 g of electrolyte. After sealing, it is stored at 60°C. Every 8 hours, the film is removed, the electrolyte on the surface is wiped off, the thickness is measured, and the film is weighed. It is then returned to the electrolyte, sealed, and stored at 60°C until the film thickness and mass remain unchanged in three consecutive tests. Excess electrolyte and lithium salt on the film are washed away with dimethyl carbonate (DMC). The film is then completely dried in an oven, and the mass of the remaining film after drying is weighed. The swelling loss rate is calculated according to the following formula:
[0219]
[0220] In the above formula, m0 represents the mass of the boron-crosslinked polymer membrane before immersion in the electrolyte, in g, and m2 represents the mass of the remaining boron-crosslinked polymer membrane after immersion in the electrolyte, followed by washing and drying, in g.
[0221] In some embodiments of the present invention, the electrolyte comprises a non-aqueous organic solvent and a lithium salt; preferably, the non-aqueous organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate; more preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, and lithium difluorosulfonylimide.
[0222] In some embodiments of the present invention, the electrolyte further includes one or more of unsaturated cyclic carbonates, fluorocyclic carbonates, cyclic sulfonates, and cyclic sulfates.
[0223] In some embodiments of the present invention, the positive electrode includes a current collector and a positive electrode coating material coated on the current collector. The current collector can be various current collectors well known to those skilled in the art, such as aluminum foil, carbon-coated aluminum foil, or aluminum-plated polymer film. The positive electrode coating material includes the above-mentioned polymer with boron crosslinking structure and the positive electrode active material.
[0224] It is understood that the aforementioned positive electrode coating material also includes positive electrode conductive agents and binders; the aforementioned positive electrode active materials include, but are not limited to, lithium nickel cobalt manganese oxide (LiNi). x Co y Mn 1-x-yO₂, where 0<x<1.0 and 0<y<1.0), lithium cobalt oxide (LiCoO₂), lithium nickel oxide (LiNiO₂), lithium manganate (LiMn₂O₄), one or more of them; the positive electrode conductive agent includes but is not limited to one or more of carbon black, carbon nanotubes (CNT), flake graphite, Ketjen black, and VGCF; the binder includes but is not limited to one or more of polyvinylidene fluoride (PVDF), copolymers of vinylidene fluoride (VF₂), and polyimide.
[0225] In some embodiments of the present invention, the negative electrode comprises a current collector and a negative electrode coating material coated on the current collector. The current collector may be various current collectors well known to those skilled in the art, such as copper foil, carbon-coated copper foil, and copper-plated polymer film; the negative electrode coating material includes the above-mentioned polymer with a boron crosslinked structure and a negative electrode active material.
[0226] It can be understood that the above negative electrode coating material further includes a negative electrode conductive agent and a binder; the above negative electrode active material includes but is not limited to artificial graphite (C), silicon-carbon, silicon oxide or mesocarbon microbeads; the conductive agent includes but is not limited to one or more of carbon black, carbon nanotubes (CNT), flake graphite, Ketjen black, and VGCF; the binder includes but is not limited to one or more of styrene-butadiene rubber emulsion (SBR), sodium carboxymethyl cellulose (CMC), and polyacrylic polymer (PAA).
[0227] In some embodiments of the present invention, the separator comprises a porous polymer film and a separator coating material coated on the porous polymer film; the above separator coating material includes the above-mentioned polymer with a boron crosslinked structure and inorganic particles. It can be understood that the above separator coating material further includes a binder, and the binder includes but is not limited to one or more of polyvinylidene fluoride (PVDF), styrene-butadiene rubber emulsion (SBR), and sodium carboxymethyl cellulose (CMC); the inorganic particles include but are not limited to at least one of alumina, boehmite, calcium carbonate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium oxide and silicon carbide.
[0228] In a second aspect, the present invention further provides a method for preparing the above gel electrolyte lithium ion battery, comprising the following steps: forming a positive electrode, a negative electrode and a separator into a cell, placing the cell in a battery case, then injecting an electrolyte to obtain a semi-finished lithium ion battery, and subjecting the semi-finished lithium ion battery to formation and degassing, then sealing the liquid injection port of the battery case to obtain the gel electrolyte lithium ion battery;
[0229] Wherein, at least one of the positive electrode, the negative electrode or the separator is prepared by the following method:
[0230] (1) The positive electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a positive electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the positive electrode; preferably, the drying temperature is 60-120℃;
[0231] (2) The negative electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a negative electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the negative electrode; preferably, the drying temperature is 60-120℃;
[0232] (3) The diaphragm is prepared by the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with diaphragm slurry, then coating the slurry onto a polymer porous membrane, and then drying to obtain the diaphragm; preferably, the drying temperature is 60-120℃.
[0233] It should be noted that the electrode slurry mentioned in this invention refers to a fluid formed by mixing and uniformly dispersing materials such as electrode active materials, conductive agents, and binders in a solvent, while the diaphragm slurry refers to a fluid formed by mixing and dispersing materials such as inorganic particles and binders in a solvent.
[0234] In some embodiments of the present invention, the sum of the weights of the boric acid compounds and the polymers containing active hydrogen functional groups accounts for 1-10% of the weight of the positive electrode slurry, based on the total weight of the positive electrode slurry being 100%.
[0235] Based on the total weight of the negative electrode slurry as 100%, the sum of the weights of the boric acid compounds and the polymers containing active hydrogen functional groups accounts for 1-10% of the weight of the negative electrode slurry.
[0236] Based on the total weight of the diaphragm slurry (100%), the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-50%.
[0237] Thirdly, the present invention also provides an electrode for a lithium-ion battery, comprising a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3, 4, 5, 6, 7 and 8.
[0238]
[0239] Wherein, R1 is selected from one of hydroxyl, alkyl, phenyl, naphthalene, or heteroaryl groups, and X1, X2, and X3 are each independently selected from one of the following groups.
[0240]
[0241] Wherein, R2 is a hydrogen atom or an alkyl group;
[0242] Among them, when X1, X2, and X3 are each independently selected At this time, O is directly connected to B, and C is directly connected to the polymer chain;
[0243] When X1, X2, and X3 are each independently selected At this time, O is directly connected to B, and S is directly connected to the polymer chain;
[0244] When X1, X2, and X3 are each independently selected At this time, N is directly connected to B, and C is directly connected to the polymer chain.
[0245] In some specific embodiments of the present invention, the heteroaryl group is selected from pyridyl, thiophenyl, pyrroleyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl.
[0246] In some specific embodiments of the present invention, the alkyl, phenyl, naphthyl, or heteroaryl group may be substituted with one or more substituents. Each substituent is independently selected from C1-6 alkyl, C1-6 haloalkyl, halogen, C1-6 alkoxy, carbonyl, benzyloxy, cyano, or ester groups.
[0247] In some specific embodiments of the present invention, each of the substituents is independently selected from C1-4 alkyl, C1-4 haloalkyl, halogen, C1-4 alkoxy, carbonyl, benzyloxy, cyano or ester.
[0248] In some specific embodiments of the present invention, each of the substituents is independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl, bromoethyl, fluoroethyl, chloroethyl, 1,1-difluoroethyl, 1,1-dichloroethyl, fluoropropyl, chloropropyl, trifluoromethyl, 1,1-difluoropropyl, 1,1,1-trifluoropropyl, fluorobutyl, chlorobutyl, 1,1-difluorobutyl The following groups are listed: methyl, fluorinated, chloromeric, bromine, iodomethyl, methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, tert-butoxy, methyl ketone, formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, benzyloxy, cyano, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, tert-butyl ester, phenyl acetate, or dibutyl phthalate.
[0249] In some specific embodiments of the present invention, R1 is selected from hydroxyl, alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl; the alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl may be substituted by one or more substituents; each substituent is independently selected from C1-6 alkyl, C1-6 haloalkyl, halogen, C1-6 alkoxy, carbonyl, benzyloxy, cyano, or ester.
[0250] In some specific embodiments of the present invention, R1 is selected from hydroxyl, alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrolyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl; the alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrolyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl may be substituted by one or more substituents; each substituent is independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl, bromoethyl, fluoroethyl, chloroethyl, and 1,1-difluoroethyl. 1,1-Dichloroethyl, fluoropropyl, chloropropyl, 1,1-difluoropropyl, 1,1,1-trifluoropropyl, fluorobutyl, chlorobutyl, 1,1-difluorobutyl, fluoro, chloro, bromo, iodo, methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, tert-butoxy, methyl ketone, formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, benzyloxy, cyano, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, tert-butyl acetate, phenyl acetate, or dibutyl phthalate.
[0251] In some specific embodiments of the present invention, R1 is selected from hydroxyl, C1-6 alkyl, phenyl, halogen-substituted phenyl, alkyl-substituted phenyl, haloalkyl-substituted phenyl, cyano-substituted phenyl, carbonyl-substituted phenyl, alkoxy-substituted phenyl, naphthyl, pyridyl, thiophenyl, halogen-substituted thiophenyl, carbonyl-substituted thiophenyl, pyrroleyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, halogen-substituted pyrimidinyl, furanyl, indoleyl, or ester-substituted indoleyl.
[0252] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, fluorinated phenyl, chlorosubstituted phenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, butylphenyl, isobutylphenyl, tert-butylphenyl, chlorobenzyl, bromophenylethyl, fluoromethyl substituted phenyl, difluoromethyl substituted phenyl, trifluoromethyl substituted phenyl, chloromethyl substituted phenyl, bromomethyl substituted phenyl, bromoethyl substituted phenyl, cyano substituted phenyl, aldehyde substituted phenyl, methoxy substituted phenyl, ethoxy substituted phenyl, propoxy substituted phenyl, butoxy substituted phenyl, naphthyl, pyridyl, thiophenyl, fluorinated thiophenyl, chlorosubstituted thiophenyl, methyl ketone substituted thiophenyl, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, fluorinated pyrimidinyl, bromosubstituted pyrimidinyl, furanyl, indole, or tert-butyl ester substituted indole.
[0253] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, etc.
[0254]
[0255] It should be noted that the dashed line in the above selection of R1 group represents a direct connection with B.
[0256] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of the following groups.
[0257]
[0258] R2 is a hydrogen atom or a C1-6 alkyl group.
[0259] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of the following groups.
[0260]
[0261] Wherein, R2 is a hydrogen atom, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, tert-hexyl, or tert-hexyl.
[0262] It should be noted that the wavy lines in Equations 1-6 described in this article represent polymer chains.
[0263] In some embodiments of the present invention, the polymer chain is selected from one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates.
[0264] In one specific embodiment of the present invention, an electrode for a lithium-ion battery is also provided, comprising a current collector and an electrode coating material coated on the current collector, wherein the electrode coating material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below.
[0265]
[0266] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group;
[0267] The alkyl or phenyl group may be substituted with one or more substituents. The selection of the substituents is the same as that of the alkyl, phenyl, naphthyl, or heteroaryl groups mentioned above.
[0268] In some specific embodiments of the present invention, R1 is selected from hydroxyl, C1-6 alkyl, phenyl, halogen-substituted phenyl, alkyl-substituted phenyl, haloalkyl-substituted phenyl, cyano-substituted phenyl, carbonyl-substituted phenyl, or alkoxy-substituted phenyl.
[0269] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, fluorinated phenyl, chlorosubstituted phenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, butylphenyl, isobutylphenyl, tert-butylphenyl, chlorobenzyl, bromophenylethyl, fluoromethyl substituted phenyl, difluoromethyl substituted phenyl, trifluoromethyl substituted phenyl, chloromethyl substituted phenyl, bromomethyl substituted phenyl, bromoethyl substituted phenyl, cyano substituted phenyl, aldehyde substituted phenyl, methoxy substituted phenyl, ethoxy substituted phenyl, propoxy substituted phenyl, or butoxy substituted phenyl.
[0270] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or a C1-6 alkyl group.
[0271] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, tert-hexyl, or tert-hexyl.
[0272] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; wherein the boric acid compound includes one or more of boric acid, phenylboronic acid, phenyldiboronic acid, 1,3,5-phenyltriboronic acid, alkylboronic acid, naphthaleneboronic acid, and heteroarylboronic acid.
[0273] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group, wherein the boric acid compound includes one or more of boric acid, phenylboronic acid, and alkylboronic acid, and the polymer containing an active hydrogen functional group includes one or more of polymers containing hydroxyl groups, polymers containing carboxyl groups, polymers containing sulfonic acid groups, polymers containing sulfate groups, polymers containing phosphate groups, polymers containing amine groups, and polymers containing substituted amine groups.
[0274] Specifically, the present invention obtains the electrode by mixing boric acid compounds and polymers containing active hydrogen functional groups with an electrode slurry, then coating the slurry onto a current collector, and then drying it; preferably, the drying temperature is 60-120°C.
[0275] It should be noted that, depending on the requirements, when boric acid compounds and polymers containing active hydrogen functional groups are mixed with the positive electrode slurry, the positive electrode of a lithium-ion battery is obtained; when boric acid compounds and polymers containing active hydrogen functional groups are mixed with the negative electrode slurry, the negative electrode of a lithium-ion battery is obtained.
[0276] In some embodiments of the present invention, at 25-60°C, the polymer with the boron cross-linked structure has a swelling degree greater than 50% in the electrolyte, preferably a swelling loss rate of <5%, more preferably a swelling degree of 50-10000%, further preferably a swelling degree of 100%-5000%, and even more preferably a swelling degree of 100%-1000%. When the swelling degree is less than 50%, the conductivity of the gel electrolyte formed by the polymer is very low, the internal resistance of the battery increases, thereby affecting the charge / discharge rate performance and low-temperature cycle performance of the battery; when the swelling degree is greater than 10000%, the mechanical properties of the above-mentioned polymer with the boron cross-linked structure deteriorate, and it may even dissolve in the electrolyte, losing its function as a gel electrolyte.
[0277] Fourthly, the present invention also provides a method for preparing the above-mentioned lithium-ion electrode, comprising the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with an electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the electrode; preferably, the drying temperature is 60-120°C.
[0278] In some embodiments of the present invention, the electrode slurry comprises one or more of an active material, a conductive agent, a binder, and a solvent, wherein the active material is a positive electrode active material or a negative electrode active material.
[0279] In some embodiments of the present invention, the weight percentage of the sum of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-10% based on the total weight of the electrode paste (100%).
[0280] Fifthly, the present invention also provides a separator for a lithium-ion battery, comprising a polymer porous membrane and a separator coating material coated on the polymer porous membrane, wherein the separator coating material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3, 4, 5, 6, 7 and 8.
[0281]
[0282] R1 is selected from hydroxyl, alkyl, phenyl, naphthalene, or heteroaryl groups, and X1, X2, and X3 are each independently selected from one of the following groups.
[0283]
[0284] Wherein, R2 is a hydrogen atom or an alkyl group;
[0285] Among them, when X1, X2, and X3 are each independently selected At this time, O is directly connected to B, and C is directly connected to the polymer chain;
[0286] When X1, X2, and X3 are each independently selected At this time, O is directly connected to B, and S is directly connected to the polymer chain;
[0287] When X1, X2, and X3 are each independently selected At this time, N is directly connected to B, and C is directly connected to the polymer chain.
[0288] In some specific embodiments of the present invention, the heteroaryl group is selected from pyridyl, thiophenyl, pyrroleyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl.
[0289] In some specific embodiments of the present invention, the alkyl, phenyl, naphthyl, or heteroaryl group may be substituted with one or more substituents. Each substituent is independently selected from C1-6 alkyl, C1-6 haloalkyl, halogen, C1-6 alkoxy, carbonyl, benzyloxy, cyano, or ester groups.
[0290] In some specific embodiments of the present invention, each of the substituents is independently selected from C1-4 alkyl, C1-4 haloalkyl, halogen, C1-4 alkoxy, carbonyl, benzyloxy, cyano or ester.
[0291] In some specific embodiments of the present invention, each of the substituents is independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl, bromoethyl, fluoroethyl, chloroethyl, 1,1-difluoroethyl, 1,1-dichloroethyl, fluoropropyl, chloropropyl, trifluoromethyl, 1,1-difluoropropyl, 1,1,1-trifluoropropyl, fluorobutyl, chlorobutyl, 1,1-difluorobutyl The following groups are listed: methyl, fluorinated, chloromeric, bromine, iodomethyl, methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, tert-butoxy, methyl ketone, formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, benzyloxy, cyano, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, tert-butyl ester, phenyl acetate, or dibutyl phthalate.
[0292] In some specific embodiments of the present invention, R1 is selected from hydroxyl, alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl; the alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl may be substituted by one or more substituents; each substituent is independently selected from C1-6 alkyl, C1-6 haloalkyl, halogen, C1-6 alkoxy, carbonyl, benzyloxy, cyano, or ester.
[0293] In some specific embodiments of the present invention, R1 is selected from hydroxyl, alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrolyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl; the alkyl, phenyl, naphthyl, pyridyl, thiophene, pyrrolyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, furanyl, or indoleyl may be substituted by one or more substituents; each substituent is independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl, bromoethyl, fluoroethyl, chloroethyl, and 1,1-difluoroethyl. 1,1-Dichloroethyl, fluoropropyl, chloropropyl, 1,1-difluoropropyl, 1,1,1-trifluoropropyl, fluorobutyl, chlorobutyl, 1,1-difluorobutyl, fluoro, chloro, bromo, iodo, methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, isopropoxy, tert-butoxy, methyl ketone, formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, benzyloxy, cyano, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, tert-butyl acetate, phenyl acetate, or dibutyl phthalate.
[0294] In some specific embodiments of the present invention, R1 is selected from hydroxyl, C1-6 alkyl, phenyl, halogen-substituted phenyl, alkyl-substituted phenyl, haloalkyl-substituted phenyl, cyano-substituted phenyl, carbonyl-substituted phenyl, alkoxy-substituted phenyl, naphthyl, pyridyl, thiophenyl, halogen-substituted thiophenyl, carbonyl-substituted thiophenyl, pyrroleyl, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, halogen-substituted pyrimidinyl, furanyl, indoleyl, or ester-substituted indoleyl.
[0295] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, fluorinated phenyl, chlorosubstituted phenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, butylphenyl, isobutylphenyl, tert-butylphenyl, chlorobenzyl, bromophenylethyl, fluoromethyl substituted phenyl, difluoromethyl substituted phenyl, trifluoromethyl substituted phenyl, chloromethyl substituted phenyl, bromomethyl substituted phenyl, bromoethyl substituted phenyl, cyano substituted phenyl, aldehyde substituted phenyl, methoxy substituted phenyl, ethoxy substituted phenyl, propoxy substituted phenyl, butoxy substituted phenyl, naphthyl, pyridyl, thiophenyl, fluorinated thiophenyl, chlorosubstituted thiophenyl, methyl ketone substituted thiophenyl, pyrrole, thiazolyl, oxazolyl, pyrazinyl, pyrimidinyl, fluorinated pyrimidinyl, bromosubstituted pyrimidinyl, furanyl, indole, or tert-butyl ester substituted indole.
[0296] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, etc.
[0297]
[0298] It should be noted that the dashed line in the above selection of R1 group represents a direct connection with B.
[0299] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of the following groups.
[0300]
[0301] R2 is a hydrogen atom or a C1-6 alkyl group.
[0302] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of the following groups.
[0303]
[0304] R2 can be a hydrogen atom, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, tert-hexyl, or tert-hexyl.
[0305] It should be noted that the wavy lines in Equations 1-6 described in this article represent polymer chains.
[0306] In some embodiments of the present invention, the polymer chain is selected from one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates.
[0307] In one specific embodiment of the present invention, a separator for a lithium-ion battery is also provided, comprising a polymer porous membrane and a separator coating material coated on the polymer porous membrane, wherein the separator coating material contains a polymer having a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below.
[0308]
[0309] R1 is selected from hydroxyl, alkyl or phenyl, and X1, X2 and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom or an alkyl group;
[0310] Preferably, the polymer porous membrane is a polyolefin microporous membrane or a nonwoven fabric.
[0311] The alkyl or phenyl group may be substituted with one or more substituents. The selection of the substituents is the same as that of the alkyl, phenyl, naphthyl, or heteroaryl groups mentioned above.
[0312] In some specific embodiments of the present invention, R1 is selected from hydroxyl, C1-6 alkyl, phenyl, halogen-substituted phenyl, alkyl-substituted phenyl, haloalkyl-substituted phenyl, cyano-substituted phenyl, carbonyl-substituted phenyl, or alkoxy-substituted phenyl.
[0313] In some specific embodiments of the present invention, R1 is selected from hydroxyl, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, fluorinated phenyl, chlorosubstituted phenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, butylphenyl, isobutylphenyl, tert-butylphenyl, chlorobenzyl, bromophenylethyl, fluoromethyl substituted phenyl, difluoromethyl substituted phenyl, trifluoromethyl substituted phenyl, chloromethyl substituted phenyl, bromomethyl substituted phenyl, bromoethyl substituted phenyl, cyano substituted phenyl, aldehyde substituted phenyl, methoxy substituted phenyl, ethoxy substituted phenyl, propoxy substituted phenyl, or butoxy substituted phenyl.
[0314] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or a C1-6 alkyl group.
[0315] In some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from O and NR2, wherein R2 is a hydrogen atom, methyl, ethyl, propyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, tert-hexyl, or tert-hexyl.
[0316] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group, wherein the boric acid compound includes one or more of boric acid, phenylboronic acid, phenyldiboronic acid, 1,3,5-phenyltriboronic acid, alkylboronic acid, naphthaleneboronic acid, and heteroarylboronic acid.
[0317] In some embodiments of the present invention, the polymer having a boron crosslinked structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; wherein the boric acid compound includes one or more of boric acid, phenylboronic acid and alkylboronic acid.
[0318] The heteroaryl group in the heteroarylboronic acid is selected from pyridyl, pyrazinyl, pyrimidinyl, furanyl, pyrroleyl, thiophenyl, thiazolyl, or oxazolyl.
[0319] The phenyl, alkyl, naphthyl, and heteroaryl groups in the phenylboronic acid, alkylboronic acid, naphthylboronic acid, and heteroarylboronic acid can be replaced by one or more substituents. The selection of the substituents is the same as the selection of the alkyl, phenyl, naphthyl, or heteroaryl substituents mentioned above.
[0320] Preferably, phenylboronic acid includes, but is not limited to, 5-chloro-2-methoxyphenylboronic acid, 4-cyanophenylboronic acid, 5-aldehyde-2-methoxyphenylboronic acid, 4-isopropylphenylboronic acid, 2-chloro-4-methylphenylboronic acid, 3-chloro-5-trifluoromethylphenylboronic acid, or 4-benzyloxy-3-methoxyphenylboronic acid; preferably, phenyldiboronic acid includes, but is not limited to, 1,3-phenyldiboronic acid and / or 1,4-phenyldiboronic acid; preferably, alkylboronic acid includes, but is not limited to, methylboronic acid, ethylboronic acid, propylboronic acid, isopropylboronic acid, n-butylboronic acid, isobutylboronic acid, and tert-butylboronic acid. Or fluoromethylboronic acid; preferably, naphthaleneboronic acid includes, but is not limited to, 1-naphthaleneboronic acid, 2-naphthaleneboronic acid, 1,5-dinaphthaleneboronic acid or 2,6-dinaphthaleneboronic acid; preferably, heteroarylboronic acid includes, but is not limited to, 3-pyridineboronic acid, 2-fluoro-3-pyridineboronic acid, 2-bromopyridine-4-boronic acid, 2-thiopheneboronic acid, (4-fluorothiophene-2-yl)boronic acid, 5-acetyl-2-thiopheneboronic acid, 2-chlorothiophene-3-boronic acid, 2-furanboronic acid, 2-pyrroloboronic acid, 3-quinolineboronic acid, 2-imidazoliumboronic acid or N-(BOC)-7-fluoroindole-2-boronic acid.
[0321] The polymer containing active hydrogen functional groups includes one or more of the following: polymers containing hydroxyl groups, polymers containing carboxyl groups, polymers containing sulfonic acid groups, polymers containing sulfate groups, polymers containing phosphate groups, polymers containing amine groups, and polymers containing substituted amine groups.
[0322] The polymer containing active hydrogen functional groups includes one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates. Preferably, the polymers containing active hydrogen functional groups include one or more of polyolefins, polyethers, polyesters, polyamides, and polycarbonates.
[0323] Specifically, the present invention obtains a membrane containing a boron cross-linked polymer by mixing boric acid compounds and polymers containing active hydrogen functional groups with a membrane slurry, followed by coating and drying.
[0324] In some embodiments of the present invention, at 25-60°C, the polymer with the boron cross-linked structure has a swelling degree greater than 50% in the electrolyte, preferably a swelling loss rate of <5%, more preferably a swelling degree of 50-10000%, further preferably a swelling degree of 100%-5000%, and even more preferably a swelling degree of 100%-1000%. When the swelling degree is less than 50%, the conductivity of the gel electrolyte formed by the polymer is very low, the internal resistance of the battery increases, thereby affecting the charge / discharge rate performance and low-temperature cycle performance of the battery; when the swelling degree is greater than 10000%, the mechanical properties of the above-mentioned polymer with the boron cross-linked structure deteriorate, and it may even dissolve in the electrolyte, losing its function as a gel electrolyte.
[0325] In a sixth aspect, the present invention also provides a method for preparing the separator of the above-mentioned lithium-ion battery, comprising the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a separator slurry, then coating the slurry onto a polymer porous membrane, and then drying to obtain the separator; preferably, the drying temperature is 60-120°C.
[0326] In some embodiments of the present invention, the diaphragm slurry comprises inorganic particles and / or binders and solvents.
[0327] Based on the total weight of the diaphragm slurry as 100%, the sum of the weights of the boric acid compounds and the polymers containing active hydrogen functional groups accounts for 1-50% of the weight of the diaphragm slurry.
[0328] The present application is further illustrated below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0329] All raw materials and reagents used in this invention were purchased from mainstream manufacturers on the market. Those without specified manufacturers or concentrations are all analytical grade raw materials or reagents that are routinely available. There are no particular restrictions as long as they achieve the intended effect. The instruments and equipment used in this embodiment were all purchased from major manufacturers on the market. There are no particular limitations as long as they achieve the intended effect. Where specific techniques or conditions are not specified in this embodiment, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions.
[0330] Reagents:
[0331] Adipic acid, ethylene glycol, hexamethylenediamine, ethylenediamine, acrylonitrile, butyl acrylate, glycidyl methacrylate, p-styrene sulfonic acid, acrylic acid, acrylamide, triethylene glycol, polyethylene glycol PEG400, polyethylene glycol PEG1000, polypropylene glycol PPG2000, polypropylene glycol PPG4000, polyethylene glycol PEG50000, decaglycerol, dipentaerythritol, pentaerythritol, caprolactone, N,N-dimethylformamide, sulfuric acid, ethylene carbonate, propylene carbonate, boric acid, phenylboronic acid, 1,4-phenylenediboric acid, pyromellitic acid, pyromellitic tetracarboxylic acid, chlorosulfonic acid, LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent (Super) Li), PVDF binder ( 5130), N-methylpyrrolidone, artificial graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber latex (SBR) (50% solids), alumina powder, porous polyethylene film, lithium hexafluorophosphate, ethylene carbonate (EC), ethyl methyl carbonate (EMC), vinylene carbonate, 1,3-propane sulfonate lactone, etc. were all purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0332] LiNi 0.8 Co 0.1 Mn 0.1 O2 was purchased from Hubei Rongbai Lithium Battery Materials Co., Ltd.;
[0333] Conductive agent (Super) Li), PVDF binder ( 5130) was purchased from SOLVAY (SHANGHAI) Co., Ltd.
[0334] The artificial graphite was purchased from Tianjin BTR New Energy Technology Co., Ltd.
[0335] Styrene-butadiene rubber latex (SBR) (50% solids), alumina powder, polyethylene porous film, lithium hexafluorophosphate, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and vinylene carbonate were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0336] The present invention will now be described in more detail using various preparation examples, embodiments, and comparative examples, but the scope of the present invention is not limited to these examples. It should be noted that, unless otherwise specified, all percentages, parts, and ratios used in the present invention are based on mass.
[0337] Preparation Example 1
[0338] 1.1 Preparation of oligomers
[0339] 146 g of adipic acid (1 mol) and 68.2 g of ethylene glycol (1.1 mol) were added to a reaction vessel, with a molar ratio of adipic acid to ethylene glycol of 1:1.1. Then, 0.86 g of p-toluenesulfonic acid was added as a catalyst. The reaction was carried out under vacuum at 160 °C for 10 h. The mixture was washed with deionized water and then dried at 90 °C for 5 h to obtain hydroxyl-containing polyester oligomer 1, with the following structural formula:
[0340]
[0341] 1.2 Preparation of polymers with boron crosslinking structures
[0342] 180g of oligomer 1 (0.1mol) and 4.2g of boric acid (0.067mol) were added to a reaction vessel. The molar ratio of oligomer 1 to boric acid was 3:2. Methylpyrrolidone (NMP) was added as a solvent at 100% of the total mass of the reaction raw materials. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 80°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0343] Preparation Example 2
[0344] 2.1 Preparation of oligomers
[0345] 13.6 g of dried pentaerythritol (0.1 mol) and 91.5 g of caprolactone monomer (0.8 mol) were added to a reaction vessel, with a molar ratio of pentaerythritol to caprolactone of 1:8. Then, 100% of the total mass of N,N-dimethylformamide (DMF) was added as a solvent, and 0.3% of the total mass of sulfuric acid was added as a catalyst. The reaction was carried out at 100 °C for 24 h, followed by vacuum drying at 90 °C for 5 h to obtain hydroxyl-containing polyester oligomer 2, with the following structural formula:
[0346]
[0347] 2.2 Preparation of polymers with boron crosslinking structures
[0348] 105g of oligomer 2 (0.1mol) and 8.24g of boric acid (0.13mol) were added to the reactor. The molar ratio of oligomer 2 to boric acid was 3:4. Then, 100% of NMP relative to the total mass of the reactants was added as a solvent. The mixture was stirred and dissolved thoroughly at room temperature. The temperature was raised to 90°C and vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. Vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0349] Preparation Example 3
[0350] 3.1 Preparation of oligomers
[0351] 2.54 g of dried dipentaerythritol (0.01 mol) and 183.6 g of propylene carbonate monomer (1.8 mol) were added to a reaction vessel, with a molar ratio of dipentaerythritol to propylene carbonate of 1:180. Then, 150% NMP (by mass of the reactants) was added as a solvent, and 0.3% stannous octoate (by mass of the reactants) was added as a catalyst. The reaction was carried out at 90 °C under nitrogen protection for 12 h. After stopping the reaction and cooling to 0 °C, 6.99 g of chlorosulfonic acid (HSO3Cl, 0.06 mol) was added, with a molar ratio of chlorosulfonic acid to dipentaerythritol of 6:1. The product was washed with water and dried to obtain sulfate-containing polycarbonate oligomer 3, with the following structural formula:
[0352]
[0353] 3.2 Preparation of polymers with boron crosslinking structures
[0354] 768g of oligomer 3 (0.04mol) and 15g of phenylboronic acid (0.12mol) were added to a reaction vessel. The molar ratio of oligomer 3 to phenylboronic acid was 1:3. Then, 100% of NMP relative to the total mass of the reaction raw materials was added as a solvent. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 10 hours, almost no water was precipitated. The vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0355] Preparation Example 4
[0356] 4.1 Preparation of oligomers
[0357] 31 g of dried ethylene glycol (0.5 mol) and 264 g of ethylene carbonate monomer (3 mol) were added to a reaction vessel, with a molar ratio of ethylene glycol to ethylene carbonate of 1:6. Then, 100% DMF (by mass of the reactants) and 0.5% stannous octoate (by mass of the reactants) were added as a solvent and as a catalyst, respectively. The reaction was carried out at 90 °C under nitrogen protection for 12 h. Subsequently, 98 g of phosphoric acid (1 mol) was added, with a molar ratio of phosphoric acid to ethylene glycol of 2:1. The reaction was carried out overnight at 90 °C, followed by vacuum drying to obtain polycarbonate oligomer 4 containing phosphate groups, with the following structural formula:
[0358]
[0359] 4.2 Preparation of polymers with boron crosslinking structures
[0360] 150g of oligomer 4 (0.2mol) and 16.5g of boric acid (0.27mol) were added to a reaction vessel. The molar ratio of oligomer 4 to boric acid was 0.74. Then, 100% of NMP relative to the total mass of the reaction raw materials was added as a solvent. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 10 hours, almost no water was precipitated. The vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0361] Preparation Example 5
[0362] 5.1 Preparation of oligomers
[0363] 105 g of dried trimesic acid (0.5 mol) and 64 g of hexamethylenediamine (0.55 mol) were added to a reaction vessel, with a molar ratio of trimesic acid to hexamethylenediamine of 1:1.1. The reaction was carried out at 250 °C under vacuum for 12 h to obtain polyamide oligomer 5 containing amine and carboxyl groups, with the following structural formula:
[0364]
[0365] 5.2 Preparation of polymers with boron crosslinking structures
[0366] 63.6 g of oligomer 5 (0.02 mol) and 10 g of 1,4-phenylenediboric acid (0.06 mol) were added to a reaction vessel. The molar ratio of oligomer 5 to 1,4-phenylenediboric acid was 1:3. Then, 100% of NMP relative to the total mass of the reactants was added as a solvent. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 10 hours, almost no water was precipitated. The vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0367] Preparation Example 6
[0368] 6.1 Preparation of oligomers
[0369] 267 g of dried pyromellitic acid (1.05 mol) and 60 g of ethylenediamine (1 mol) were added to a reaction vessel, with a molar ratio of pyromellitic acid to ethylenediamine of 1.05:1. The reaction was carried out at 250 °C under vacuum for 12 h to obtain a carboxyl-containing polyamide oligomer 6, with the following structural formula:
[0370]
[0371] 6.2 Preparation of polymers with boron crosslinking structures
[0372] 123g of oligomer 6 (0.02mol) and 36g of 1,4-phenylenediboric acid (0.215mol) were added to a reaction vessel. The molar ratio of oligomer 6 to 1,4-phenylenediboric acid was 1:10.75. Then, 200% of the total mass of the reactants was added as a solvent. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 10 hours, almost no water was precipitated. The vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0373] Preparation Example 7
[0374] 7.1 Preparation of oligomers
[0375] 24 g of benzoyl peroxide (BPO, 0.1 mol), 85 g of acrylamide (AM, 1.2 mol), 230 g of butyl acrylate (BA, 1.8 mol), and 183 g of styrene sulfonic acid (SSA, 1 mol) were added to a reaction vessel in a molar ratio of BPO, AM, BA, and SSA of 1:12:18:10. Then, 200% NMP (based on the total mass of the reactants) was added as a solvent. The reaction was carried out at 80 °C under nitrogen protection for 10 h. The reaction was then stopped, and the mixture was dried under vacuum to obtain polyolefin oligomer 7 containing amino and sulfonic acid groups, with the following structural formula:
[0376]
[0377] 7.2 Preparation of polymers with boron crosslinking structures
[0378] 100g of oligomer 7 (0.02mol) and 9.3g of boric acid (0.15mol) were added to a reaction vessel. The molar ratio of oligomer 7 to boric acid was 1:7.5. Then, 200% of NMP relative to the total mass of the reaction raw materials was added as a solvent. The mixture was stirred and dissolved thoroughly at room temperature. The temperature was raised to 100℃ and vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. Vacuuming and heating were stopped, and the NMP solvent was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0379] Preparation Example 8
[0380] 8.1 Preparation of oligomers
[0381] 16.4 g of benzoyl peroxide (AIBN, 0.1 mol), 53 g of acrylonitrile (AN, 1.0 mol), 142 g of glycidyl methacrylate (GMA, 1.0 mol), and 36 g of acrylic acid (AA, 0.5 mol) were added to a reaction vessel in a molar ratio of AIBN, AN, GMA, and AA of 1:10:10:5. Then, 200% NMP (based on the total mass of the reactants) was added as a solvent. The reaction was carried out at 80 °C under nitrogen protection for 10 h. Next, 50% water (based on the total mass of the reactants) was added, and the reaction was refluxed at 100 °C. The reaction was stopped when the solution became completely transparent, and the mixture was dried under vacuum to obtain a polyolefin oligomer 8 containing hydroxyl and carboxyl groups, with the following structural formula:
[0382]
[0383] 8.2 Preparation of polymers with boron crosslinking structures
[0384] 100g of oligomer 8 (0.04mol) and 20g of boric acid (0.323mol) were added to a reaction vessel. The molar ratio of oligomer 8 to boric acid was 0.124:1. Water, which was 200% of the total mass of the reactants, was added as a solvent. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were stopped, and the solvent NMP was removed by vacuum drying to obtain a polymer with a boron crosslinked structure.
[0385] Preparation Example 9
[0386] 9.1 Preparation of oligomers
[0387] 80 g of polyethylene glycol (PEG400, 0.2 mol) and 49 g of 1,3-propanesulfonate lactone (1,3-PS, 0.4 mol) were added to a reaction vessel. The molar ratio of PEG to 1,3-PS was 1:2. Then, 100% NMP relative to the total mass of the reactants was added as a solvent. The reaction was carried out at 40 °C for 24 h. After removing the solvent NMP and water, the product was dried under vacuum to obtain polyether oligomer 9 containing sulfonic acid groups. The structural formula is as follows:
[0388]
[0389] 9.2 Preparation of polymers with boron crosslinking structures
[0390] 129 g of oligomer 9 (0.2 mol) and 16.6 g of 1,4-phenylenediboric acid (0.1 mol) were added to a reaction vessel. The molar ratio of oligomer 9 to 1,4-phenylenediboric acid was 2:1. Water was then added as a solvent at 100% of the total mass of the reactants. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0391] Preparation Example 10
[0392] 10.1 Preparation of oligomers
[0393] Oligomer 10 is a commercially available polyether-based decaglycerol containing multiple hydroxyl groups, with the following molecular structure:
[0394]
[0395] 10.2 Preparation of polymers with boron crosslinking structures
[0396] 76g of oligomer 10 (0.1mol) and 12.36g of boric acid (0.2mol) were added to a reaction vessel. The molar ratio of oligomer 10 to boric acid was 1:2. Water was added as a solvent at 100% of the total mass of the reaction raw materials. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0397] Preparation Example 11
[0398] 11.1 Preparation of oligomers
[0399] Oligomer 11 is polyethylene glycol PEG400 (commercially available).
[0400] 11.2 Preparation of polymers with boron crosslinking structures
[0401] 80g of oligomer 11 (0.2mol) and 9g of boric acid (0.146mol) were added to a reaction vessel. The molar ratio of oligomer 11 to boric acid was 1.37:1. Water was added as a solvent at 100% of the total mass of the reactants. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0402] Preparation Example 12
[0403] 12.1 Preparation of oligomers
[0404] Oligomer 12 is polyethylene glycol PEG1000 (commercially available).
[0405] 12.2 Preparation of polymers with boron crosslinking structures
[0406] 100g of oligomer 12 (0.1mol) and 4g of boric acid (0.064mol) were added to a reaction vessel. The molar ratio of oligomer 12 to boric acid was 1.56:1. Water was added as a solvent at 100% of the total mass of the reactants. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0407] Preparation Example 13
[0408] 13.1 Preparation of oligomers
[0409] Oligomer 13 is polypropylene glycol PPG2000 (commercially available).
[0410] 13.2 Preparation of polymers with boron crosslinking structures
[0411] 20g of oligomer 13 (0.01mol) and 0.36g of boric acid (0.006mol) were added to a reaction vessel. The molar ratio of oligomer 13 to boric acid was 1.67:1. Water was added as a solvent at 100% of the total mass of the reactants. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0412] Preparation Example 14
[0413] 14.1 Preparation of oligomers
[0414] Oligomer 14 is polypropylene glycol PPG4000 (commercially available).
[0415] 14.2 Preparation of polymers with boron crosslinking structures
[0416] 40g of oligomer 14 (0.01mol) and 0.36g of boric acid (0.006mol) were added to a reaction vessel. The molar ratio of oligomer 14 to boric acid was 1.67:1. Water was then added as a solvent at 100% of the total mass of the reactants. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0417] Preparation Example 15
[0418] 15.1 Preparation of oligomers
[0419] Oligomer 15 is polyethylene glycol PEG50000 (commercially available).
[0420] 15.2 Preparation of polymers with boron crosslinking structures
[0421] 500g of oligomer 15 (PEG50000, 0.01mol) and 0.3g of boric acid (0.005mol) were added to a reaction vessel. The molar ratio of oligomer 15 to boric acid was 2:1. Water was then added as a solvent at 100% of the total mass of the reaction raw materials. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100℃ and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0422] Preparation Example 16
[0423] 16.1 Preparation of oligomers
[0424] Oligomer 16 is a commercially available triethylene glycol (TEG) containing two hydroxyl groups, with the following molecular structure:
[0425]
[0426] 16.2 Preparation of polymers with boron crosslinking structures
[0427] 200g of oligomer 16 (TEG, 1.33mol) and 55g of boric acid (0.89mol) were added to a reaction vessel. The molar ratio of oligomer 16 to boric acid was 3:2. Water was added as a solvent at 100% of the total mass of the reactants. The mixture was stirred thoroughly at room temperature to dissolve the polymer. The temperature was raised to 100°C and a vacuum was applied to remove water. After about 8 hours, almost no water was precipitated. The vacuuming and heating were then stopped to obtain a polymer with a boron crosslinked structure.
[0428] It should be noted that there are no particular limitations on the amount of solvents such as water, DMF, and NMP used in the above preparation examples. As long as they can achieve the dissolution effect and facilitate subsequent drying, the amount can be, for example, 100%-500% of the total mass of the reaction raw materials.
[0429] The properties of polymers with boron crosslinking structures were tested using the following method, and the results are shown in Table 1.
[0430] (1) Determination of molecular weight and molecular weight distribution of oligomers: The absolute molecular weight and molecular weight distribution of oligomers were determined by gel permeation chromatography-laser light scattering (GPC-MALLS). The gel chromatograph was a Waters 1515 GPC gel chromatograph and the light scattering detector was a DAWN HELEOS-II light scattering detector from Wyatt.
[0431] (2) Determination of swelling degree:
[0432] A 30 μm thick, 16 mm x 16 mm circular film was fabricated from a polymer with a boron cross-linked structure. The mass of the film was measured, and the film was immersed in 10 g of electrolyte. After sealing, it was stored at 60 °C. Every 8 hours, the film was removed, the electrolyte on the surface was wiped off, the thickness was measured, and the film was weighed. The film was then returned to the electrolyte, sealed, and stored at 60 °C again. This process was repeated until the thickness and mass of the film remained unchanged for three consecutive tests. At this point, the polymer film with the boron cross-linked structure was considered to have reached swelling equilibrium. The degree of swelling was calculated using the following formula:
[0433]
[0434] In the above formula, m0 represents the mass of the polymer membrane with boron cross-linking structure before immersion in the electrolyte, and m1 represents the mass of the polymer membrane with boron cross-linking structure after immersion in the electrolyte and reaching swelling equilibrium.
[0435] The electrolyte was prepared as follows: Lithium hexafluorophosphate (LiPF6) was dissolved in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a glove box with a dew point below -40°C (the volume ratio of EC to EMC was 3:7) to prepare an electrolyte with a LiPF6 concentration of 1.2 mol / L. Then, 1.5% vinylene carbonate (VC) and 1% 1,3-propanesulfonate lactone (1,3-PS) were added according to the total weight of the electrolyte to obtain the desired electrolyte.
[0436] (3) Determination of swelling loss rate:
[0437] A 30 μm thick, 16 mm * 16 mm circular film was fabricated from a polymer with a boron crosslinking structure. The mass of the film was measured, and the film was immersed in 10 g of electrolyte. After sealing, it was stored at 60 °C. Every 8 hours, the film was removed, the electrolyte on the surface was wiped off, the thickness was measured, and the film was weighed. The film was then returned to the electrolyte, sealed, and stored at 60 °C until the thickness and mass of the film remained unchanged in three consecutive tests. Excess electrolyte and lithium salt on the film were washed away with dimethyl carbonate (DMC), and the film was completely dried in an oven. The mass of the remaining film after drying was measured, and the swelling loss rate was calculated according to the following formula:
[0438]
[0439] In the above formula, m0 represents the mass of the boron-crosslinked polymer membrane before immersion in the electrolyte, in g, and m2 represents the mass of the remaining boron-crosslinked polymer membrane after immersion in the electrolyte, followed by washing and drying, in g.
[0440] The electrolyte was prepared as follows: Lithium hexafluorophosphate (LiPF6) was dissolved in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a glove box with a dew point below -40°C (the volume ratio of EC to EMC was 3:7) to prepare an electrolyte with a LiPF6 concentration of 1.2 mol / L. Then, 1.5% vinylene carbonate (VC) and 1% 1,3-propanesulfonate lactone (1,3-PS) were added according to the total weight of the electrolyte to obtain the desired electrolyte.
[0441] Example 1
[0442] 1. Battery manufacturing
[0443] 1.1 Preparation of the positive electrode plate
[0444] LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, carbon black conductive agent (Super) Li), PVDF binder ( 5130) was mixed in a weight ratio of 96.5:1.5:2 and added to a double planetary mixer. The total weight of the positive electrode active material, carbon black conductive agent, and binder was 1 kg. 0.5 kg of N-methylpyrrolidone (NMP) was added and stirred thoroughly. Then, 20 g (0.011 mol, of which the molar amount of hydroxyl groups was 0.022 mol) of oligomer 1 and 0.467 g (0.007 mol) of boric acid were added and stirred until homogeneous. The mixture was then filtered through a filter screen to obtain a slurry with a solid content of 65%. The slurry was then coated onto both sides of an aluminum foil with a thickness of 12 μm using an extrusion coating machine. After baking and hot rolling, a positive electrode plate was obtained. The areal density of the single-sided coating of the positive electrode plate was 20 mg / cm³. 2 The single-sided coating thickness is 58μm. The obtained positive electrode plate is dried in a vacuum oven at 120℃ for more than 24 hours to obtain the positive electrode.
[0445] 1.2 Preparation of the negative electrode
[0446] The negative electrode active material is artificial graphite, and the conductive agent is carbon black (Super). Li and sodium carboxymethyl cellulose (CMC) were mixed at a weight ratio of 97:1.5:1.5 and then added to a double planetary mixer. The total weight of the negative electrode active material, carbon black conductive agent, and sodium carboxymethyl cellulose was 1 kg. 0.8 kg of deionized water (DIW) was added, and the solid content was set to 50%. After thorough mixing, styrene-butadiene rubber latex (SBR) with a solid content of 50% was added, accounting for 1% of the total solids of the negative electrode material. Then, 40 g of oligomer 11 (PEG400, 0.10 mol) and 4.5 g of boric acid (0.073 mol) were added. After further mixing, the mixture was filtered through a filter screen to obtain a slurry with a solid content of 45%. The slurry was then coated onto both sides of a 6 μm thick copper foil using an extrusion coating machine. After baking and hot rolling, a negative electrode plate was obtained. The areal density of the single-sided coating of the negative electrode plate was 13 mg / cm³. 2 The single-sided coating thickness is 79μm, and the resulting negative electrode plate is dried in a vacuum oven at 120℃ for more than 24 hours.
[0447] 1.3 Preparation of the diaphragm
[0448] Alumina powder (D50 of 1.5 μm) and sodium carboxymethyl cellulose (CMC) were mixed at a weight ratio of 99.25:0.75 and then added to 1.5 kg of deionized water (DIW). The total weight of the alumina powder and sodium carboxymethyl cellulose (CMC) was 1 kg. The mixture was stirred and ground in a stirring mill until the particle size of the alumina was below 2 μm. Then, it was transferred to a mixing tank, and styrene-butadiene rubber latex with a solid content of 50% (1.2% of the total solids of the diaphragm coating material) was added. 40 g of oligomer 10 (0.053 mol) and 6.5 g of boric acid (0.11 mol) were also added. After stirring evenly, the mixture was filtered through a filter screen to obtain a slurry with a solid content of 10%. The slurry was then coated onto one surface of a 9 μm thick polyethylene porous membrane (porosity of 45%) using gravure printing. This step was repeated to coat the other surface of the polyethylene porous membrane with the slurry. After drying, a composite porous membrane with a single-sided inorganic coating thickness of 3 μm was obtained. The total thickness of the composite porous membrane was 15 μm, and the obtained membrane was dried in a vacuum oven at 80°C for more than 48 hours.
[0449] 1.4 Preparation of dry cell
[0450] The positive electrode plate, negative electrode plate, and separator are cut into specific shapes. The active material area on the positive electrode plate is 48mm × 44mm, the active material area on the negative electrode plate is 52mm × 46mm, and the separator is 56mm × 50mm. Current collector leads are left on both the positive and negative electrode plates. Then, the plates are stacked layer by layer in the order of negative electrode plate, separator, positive electrode plate, separator, negative electrode plate, ..., resulting in a total of 18 positive electrode plates and 19 negative electrode plates, with the outermost layer being the negative electrode plate. The current collector leads of the positive electrode plates are then welded together using an ultrasonic welder, and a positive electrode tab is welded on. Similarly, the current collector leads of the negative electrode plates are welded together using an ultrasonic welder, and a negative electrode tab is welded on. This yields the stacked plate.
[0451] The aforementioned stacked body is placed into a packaging bag made of two stamped aluminum-plastic films, and the hot melt adhesive on the tabs is fused together with the packaging bag by hot melting. The tabs are led out of the packaging bag, and an air bladder and liquid injection port are left on one side of the packaging bag, thus obtaining a dry cell.
[0452] 1.5 Preparation of Electrolyte
[0453] Lithium hexafluorophosphate (LiPF6) was dissolved in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio of EC to EMC 3:7) in a glove box with a dew point below -40°C to prepare an electrolyte with a LiPF6 concentration of 1.2 mol / L. Then, 1.5% by weight of vinylene carbonate (VC) and 1% by weight of 1,3-propanesulfonate lactone (1,3-PS) were added to obtain the desired electrolyte.
[0454] 1.6 Battery Preparation
[0455] The electrolyte was injected into the dry cell through the injection port in a glove box with a dew point below -40°C. After standing for 24 hours, the injection port outside the air bladder was sealed with a vacuum heat sealer, and the gas in the cell was extracted to obtain the battery. The weight of the unformed cell was weighed, and the weight of the dry cell was subtracted to obtain the weight of the injected electrolyte.
[0456] 1.7 Battery Formation
[0457] The above-mentioned battery cell is formed using a charging and discharging device. First, it is charged at a constant current of 0.05C to 3.6V. Then, a vacuum heat sealer is used to evacuate and seal the gasket and cut off the gasket. Next, it is charged at a constant current of 0.2C to 4.2V. Then, it is charged at a constant voltage until the current drops to 0.05C. Finally, it is discharged at a constant current of 0.2C to 3.0V, thus obtaining a well-formed battery cell, which is the gel electrolyte lithium-ion battery of the present invention.
[0458] 2. Battery testing
[0459] 2.1 Initial discharge capacity test
[0460] At room temperature, the formed batteries were charged at a constant current of 1C to 4.2V, then charged at a constant voltage until the current dropped to 0.05C, and finally discharged at a constant current of 1C to 3.0V to obtain the initial discharge capacity (Ah). Then, a portion of the batteries underwent high-temperature storage testing, while the other portion underwent charge-discharge cycle testing.
[0461] 2.2 High-temperature storage test
[0462] At room temperature, the battery was charged at a constant current of 1C to 4.2V, and then charged at a constant voltage until the current dropped to 0.05C. The battery was then transferred to an oven at 60°C and stored for 7 days. The thickness of the battery was then measured and compared with the thickness before high-temperature storage. The thickness expansion rate was calculated as follows: Thickness expansion rate = (Battery thickness after high-temperature storage - Battery thickness before high-temperature storage) / Battery thickness before high-temperature storage * 100%.
[0463] After the battery cools to room temperature, it is discharged at a constant current of 1C to 3.0V. The capacity retention rate is calculated by comparing the discharge capacity obtained with the discharge capacity before high temperature storage. That is, capacity retention rate = discharge capacity after high temperature storage / discharge capacity before high temperature storage * 100%.
[0464] The battery was then charged at a constant current of 1C to 4.2V, then charged at a constant voltage until the current dropped to 0.05C, and then discharged at a constant current of 1C to 3.0V. The capacity recovery rate was calculated by comparing the discharge capacity obtained with the discharge capacity before high-temperature storage. That is, capacity recovery rate = discharge capacity after high-temperature storage / discharge capacity before high-temperature storage * 100%.
[0465] 2.3 Charge-discharge cycle test
[0466] At room temperature, the battery is charged at a constant current of 1C to 4.2V, then charged at a constant voltage until the current drops to 0.05C, and then discharged at a constant current of 1C to 3.0V. This cycle is repeated for 1000 cycles. The discharge capacity retention rate is calculated by comparing the discharge capacity of the last discharge with that of the first discharge.
[0467] 2.4 Needle prick test
[0468] The battery needle penetration safety test was conducted in accordance with GB / T 31485-2015. A steel needle with a diameter of 8 mm was used to penetrate the battery along the direction perpendicular to the electrode plate at a speed of 25 mm / s and remain inside for 1 hour.
[0469] The test results are shown in Table 2.
[0470] Example 2
[0471] Except for the addition of 30g oligomer 7 (0.006mol) and 2.79g boric acid (0.045mol) during the fabrication of the positive electrode plate, the addition of 50g oligomer 12 (PEG1000, 0.05mol) and 2g boric acid (0.032mol) during the fabrication of the negative electrode plate, and the addition of 80g oligomer 10 (0.105mol) and 26.3g boric acid (0.426mol) during the fabrication of the separator, the other steps are the same as in Example 1.
[0472] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0473] Example 3
[0474] Except for the addition of 30g oligomer 3 (0.011mol) and 4g phenylboronic acid (0.033mol) during the positive electrode plate fabrication process, the addition of 20g oligomer 13 (PPG2000, 0.01mol) and 0.41g boric acid (0.0067mol) during the negative electrode plate fabrication process, and the omission of oligomer 10 and boric acid during the membrane fabrication process, the process is the same as in Example 1.
[0475] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0476] Example 4
[0477] Except for the addition of 50g oligomer 6 (0.008mol) and 14.63g 1,4-phenylenediboric acid (0.089mol) during the fabrication of the positive electrode plate, the addition of 50g oligomer 12 (PEG1000, 0.05mol) and 2g boric acid (0.032mol) during the fabrication of the negative electrode plate, and the omission of oligomer 10 and boric acid during the fabrication of the separator, the process is the same as in Example 1.
[0478] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0479] Example 5
[0480] Except for the addition of 25g oligomer 4 (0.033mol) and 2.75g boric acid (0.044mol) during the fabrication of the positive electrode plate, the absence of oligomer 11 and boric acid during the fabrication of the negative electrode plate, and the addition of 100g oligomer 11 (PEG400, 0.25mol) and 11.25g boric acid (0.183mol) during the fabrication of the separator, the process is the same as in Example 1.
[0481] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0482] Example 6
[0483] Except for the addition of 50g oligomer 5 (0.016mol) and 7.86g 1,4-phenylenediboric acid (0.047mol) during the fabrication of the positive electrode plate, the omission of oligomer 11 and boric acid during the fabrication of the negative electrode plate, and the addition of 50g oligomer 9 (0.077mol) and 6.43g 1,4-phenylenediboric acid (0.039mol) during the fabrication of the separator, the other steps are the same as in Example 1.
[0484] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0485] Example 7
[0486] Except for the addition of 80g oligomer 9 (0.124mol) and 10.3g 1,4-phenylenediboric acid (0.062mol) during the fabrication of the negative electrode plate, the addition of 50g oligomer 9 (0.078mol) and 6.43g 1,4-phenylenediboric acid (0.039mol) during the fabrication of the separator, and the omission of oligomer 1 and boric acid during the fabrication of the positive electrode plate, the process is the same as in Example 1.
[0487] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0488] Example 8
[0489] Except for the addition of 50g oligomer 12 (PEG1000, 0.05mol) and 2g boric acid (0.032mol) during the fabrication of the negative electrode plate, the addition of 50g oligomer 8 (0.02mol) and 10g boric acid (0.161mol) during the fabrication of the separator, and the omission of oligomer 1 and boric acid during the fabrication of the positive electrode plate, the process is the same as in Example 1.
[0490] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0491] Example 9
[0492] Except for the addition of 20g oligomer 14 (PPG4000, 0.005mol) and 0.18g boric acid (0.003mol) during the fabrication of the positive electrode plate, the addition of oligomer 11 and boric acid during the fabrication of the negative electrode plate, and the addition of oligomer 10 and boric acid during the fabrication of the separator, the process is the same as in Example 1.
[0493] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0494] Example 10
[0495] Except for the addition of 80g oligomer 8 (0.032mol) and 16g boric acid (0.26mol) during the fabrication of the negative electrode plate, the omission of oligomer 1 and boric acid during the fabrication of the positive electrode plate, and the omission of oligomer 10 and boric acid during the fabrication of the separator, the process is the same as in Example 1.
[0496] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0497] Example 11
[0498] Except for the addition of 50g oligomer 9 (0.077mol) and 6.43g 1,4-phenylenediboric acid (0.039mol) during the membrane fabrication process, the addition of oligomer 1 and boric acid during the positive electrode plate fabrication process, and the addition of oligomer 11 and boric acid during the negative electrode plate fabrication process, the process is the same as in Example 1.
[0499] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0500] Example 12
[0501] Except for the addition of 50g oligomer 9 (0.077mol) and 5.5g 2-fluoro-3-pyridineboronic acid (0.039mol) during the membrane fabrication process, the addition of oligomer 1 and boric acid during the positive electrode plate fabrication process, and the addition of oligomer 11 and boric acid during the negative electrode plate fabrication process, the process is the same as in Example 1.
[0502] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0503] Example 13
[0504] Except for the addition of 80g oligomer 8 (0.032mol) and 27g 1,3,5-benzenetriboronic acid (0.13mol) during the fabrication of the negative electrode plate, the omission of oligomer 1 and boric acid during the fabrication of the positive electrode plate, and the omission of oligomer 10 and boric acid during the fabrication of the separator, the process is the same as in Example 1.
[0505] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0506] Comparative Example 1
[0507] Except that oligomer 1 and boric acid are not added during the fabrication of the positive electrode plate, oligomer 11 and boric acid are not added during the fabrication of the negative electrode plate, and oligomer 10 and boric acid are not added during the fabrication of the separator, everything else is the same as in Example 1.
[0508] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0509] Comparative Example 2
[0510] Except for the addition of 50g oligomer 15 (PEG50000, 0.001mol) and 0.03g boric acid (0.0005mol) during the positive electrode plate fabrication process, the process is the same as in Example 9.
[0511] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0512] Comparative Example 3
[0513] Except for the addition of 20g of oligomer 16 (TEG, 0.133mol) and 5.5g of boric acid (0.089mol) during the fabrication of the negative electrode plate, the process was the same as in Example 10.
[0514] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0515] Comparative Example 4
[0516] Except for the addition of 120g oligomer 14 (0.03mol) and 12g boric acid (0.02mol) during the fabrication of the positive electrode plate, everything else is the same as in Example 1.
[0517] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0518] Comparative Example 5
[0519] Except for the addition of 1g oligomer 9 (0.0016mol) and 0.13g 1,4-phenylenediboric acid (0.0008mol) during the membrane fabrication process, everything else was the same as in Example 1.
[0520] The battery was tested according to the test method in Example 1, and the test results are shown in Table 2.
[0521] Table 1 Basic parameters of polymers with boron crosslinking structure
[0522]
[0523]
[0524] Note: The polymer with a cross-linked structure in Preparation Example 15 dissolved during the test.
[0525] Table 2 Battery performance test results
[0526]
[0527]
[0528] As shown in Table 1, the oligomers used in Preparation Examples 1-14 have molecular weights between 400 and 19200, and all contain multiple functional groups that can react with boric acid. These oligomers undergo esterification reactions with boric acid or phenylboronic acid to generate boron-crosslinked polymers. At 60°C, the swelling degree of the boron-crosslinked polymers in the electrolyte is 59-6700%, all greater than 50%, and the swelling loss rate is less than 5%. In contrast, the oligomers used in Preparation Examples 15 and 16 have molecular weights of 50000 and 150, respectively, and both contain only two hydroxyl groups that can react with boric acid. The swelling loss rate of the boron-crosslinked polymer in Preparation Example 15 reaches 92%, indicating that the polymer is essentially soluble in the electrolyte. The swelling degree of the boron-crosslinked polymer in Preparation Example 16 is only 17%, and the low liquid absorption rate will lead to poor ionic conductivity.
[0529] As shown in Table 2, the lithium-ion batteries obtained by adding the oligomers of the present invention and boric acid to the coating materials of the electrodes or separators in Examples 1-13 have a high-temperature storage thickness expansion rate of 2.3-3.3%, a high-temperature storage capacity retention rate of 89-93%, a high-temperature storage capacity recovery rate of 93-97%, and a room-temperature cycle capacity retention rate of 88-92% after 1000 cycles. The needle penetration test results show that none of them catch fire or explode. In Comparative Example 1, neither the oligomers nor boric acid of the present invention were added to the electrode or the separator. Its high-temperature storage performance was inferior to that of Example 1, and it caught fire during a needle penetration test. In Comparative Example 2, oligomer 15 was added to the positive electrode. The resulting boron-crosslinked polymer swelled excessively and even dissolved in the electrolyte. Its high-temperature storage performance was inferior to that of Example 9, and its capacity remained <50% during cycling. It also caught fire during a needle penetration test. In Comparative Example 3, oligomer 16 was added to the negative electrode. The resulting boron-crosslinked polymer swelled too little, and its high-temperature storage performance was significantly inferior to that of Example 10. It also caught fire during a needle penetration test. In Comparative Example 4, more than 10% oligomers and boric acid were added to the electrode. Although the battery did not catch fire or explode during a needle penetration test, its capacity remained <50% during cycling. In Comparative Example 5, 1‰ oligomers and boric acid were added to the separator. The battery's electrochemical performance and needle penetration safety were not significantly different from Comparative Example 1.
[0530] Therefore, lithium-ion batteries containing the boron-crosslinked polymer of the present invention in the electrode coating material or separator coating material have significantly improved high-temperature storage performance and safety.
[0531] In summary, this invention adds polymers containing active hydrogen functional groups and boric acid compounds to the positive electrode, negative electrode, or separator, forming a cross-linked polymer through esterification and cross-linking reactions. Upon contact with the electrolyte, this polymer absorbs the electrolyte and swells to form a gel electrolyte. This allows for the use of traditional lithium-ion battery manufacturing processes, avoiding the complex processes or electrolyte instability and difficulty in wetting the electrodes caused by adding gel polymers or their precursors to the electrolyte in existing technologies. It meets the demands of high-energy-density batteries. Furthermore, using a gel electrolyte instead of a liquid electrolyte reduces electrolyte leakage and solvent evaporation, as well as reducing contact between the electrolyte and the active material surface. This improves the high-temperature cycle performance and safety of lithium batteries, extends their lifespan, and reduces the risk of fire and explosion, demonstrating significant application potential.
[0532] While this application discloses preferred embodiments as described above, it is not intended to limit the scope of the claims. Any person skilled in the art can make various possible variations and modifications without departing from the spirit and concept of this application. Therefore, the scope of protection of this application should be determined by the scope defined in the claims. The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the invention. All modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A gel electrolyte lithium-ion battery, characterized in that, The device includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, negative electrode, or separator comprises a polymer with a boron crosslinking structure, wherein the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3, and 4 below. , R1 is selected from one of hydroxyl, alkyl, aryl or heteroaryl, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group; When X1, X2, and X3 are each independently selected from O, the groups containing O are selected from: , , or , When X1, X2, and X3 are each independently selected from NR2, the group containing NR2 is selected from... ; Wherein, the O-containing group is selected from At this time, O is directly connected to B, and C is directly connected to the polymer chain; When the O-containing group is selected from At this time, O is directly connected to B, and S is directly connected to the polymer chain; When the group containing NR2 is selected from At this time, N is directly connected to B, and C is directly connected to the polymer chain; At 25-60°C, the polymer with boron cross-linked structure exhibits a swelling degree of 50-10000% in the electrolyte; the swelling loss rate of the polymer with boron cross-linked structure in the electrolyte is <5%. The polymer with a boron crosslinking structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; based on 100% of the total weight of the positive electrode slurry, the weight percentage of the sum of the weights of the boric acid compound and the polymer containing an active hydrogen functional group is 1-10%; or, based on 100% of the total weight of the negative electrode slurry, the weight percentage of the sum of the weights of the boric acid compound and the polymer containing an active hydrogen functional group is 1-10%; or, based on 100% of the total weight of the membrane slurry, the weight percentage of the sum of the weights of the boric acid compound and the polymer containing an active hydrogen functional group is 1-50%.
2. The gel electrolyte lithium-ion battery according to claim 1, characterized in that, The device includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein at least one of the positive electrode, negative electrode, or separator comprises a polymer with a boron crosslinking structure, wherein the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3, and 4 below. , R1 is a phenyl group, and X1, X2, and X3 are each independently selected from O and NR2, where R2 is a hydrogen atom or an alkyl group.
3. The gel electrolyte lithium-ion battery according to claim 1, characterized in that, The boric acid compounds include one or more of the following: boric acid, phenylboronic acid, phenyldiboronic acid, 1,3,5-phenyltriboronic acid, alkylboronic acid, naphthaleneboronic acid, and heteroarylboronic acid. And / or, the polymer containing an active hydrogen functional group includes one or more of the following: polymers containing hydroxyl groups, polymers containing carboxyl groups, polymers containing sulfonic acid groups, polymers containing sulfuric acid groups, polymers containing phosphate groups, polymers containing amine groups, and polymers containing substituted amine groups.
4. The gel electrolyte lithium-ion battery according to claim 3, characterized in that, The polymer containing active hydrogen functional groups includes one or more of the following: polyolefins containing active hydrogen functional groups, polyethers containing active hydrogen functional groups, polyesters containing active hydrogen functional groups, polyamides containing active hydrogen functional groups, and polycarbonates containing active hydrogen functional groups.
5. The gel electrolyte lithium-ion battery according to any one of claims 1-4, characterized in that, The positive electrode includes a current collector and a positive electrode coating material coated on the current collector; And / or, the negative electrode includes a current collector and a negative electrode coating material coated on the current collector; And / or, the diaphragm comprises a polymer porous membrane and a diaphragm coating material coated on the polymer porous membrane.
6. The gel electrolyte lithium-ion battery according to claim 5, characterized in that, The positive electrode coating material includes a positive electrode active material and the polymer with a boron cross-linked structure; And / or, the negative electrode coating material includes a negative electrode active material and the polymer having a boron crosslinking structure; And / or, the diaphragm coating material comprises inorganic particles and polymers having a boron crosslinked structure.
7. The gel electrolyte lithium-ion battery according to any one of claims 1-4, characterized in that, The electrolyte comprises an organic solvent and a lithium salt.
8. The gel electrolyte lithium-ion battery according to claim 5, characterized in that, The electrolyte comprises an organic solvent and a lithium salt.
9. The gel electrolyte lithium-ion battery according to claim 6, characterized in that, The electrolyte comprises an organic solvent and a lithium salt.
10. The gel electrolyte lithium-ion battery according to claim 9, characterized in that, The organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate. And / or, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
11. The gel electrolyte lithium-ion battery according to claim 9, characterized in that, The lithium salt is lithium hexafluorophosphate.
12. The gel electrolyte lithium-ion battery according to claim 9, characterized in that, The electrolyte also includes one or more of the following: unsaturated cyclic carbonates, fluorocyclic carbonates, cyclic sulfonates, and cyclic sulfates.
13. The gel electrolyte lithium-ion battery according to claim 12, characterized in that, The unsaturated cyclic carbonate is selected from vinylene carbonate and / or vinyl ethylene carbonate. And / or, the fluorocyclic carbonate is selected from at least one of fluoroethylene carbonate, trifluoromethyl ethylene carbonate, or difluoroethylene carbonate. And / or, the cyclic sulfonyl lactone is selected from at least one of 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, and propenyl-1,3-sulfonyl lactone. And / or, the cyclic sulfate ester is selected from at least one of vinyl sulfate, propylene sulfate, and 4-methylvinyl sulfate.
14. The method for preparing a gel electrolyte lithium-ion battery according to any one of claims 1-13, characterized in that, The process includes the following steps: after forming the positive electrode, negative electrode and separator into a cell, place it in the battery casing, then inject electrolyte to obtain a semi-finished lithium-ion battery; after forming and venting the semi-finished lithium-ion battery, seal the electrolyte injection port of the battery casing to obtain a gel electrolyte lithium-ion battery. Wherein, at least one of the positive electrode, negative electrode, or separator is prepared according to the following method: (1) The positive electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a positive electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the positive electrode; (2) The negative electrode is prepared by the following steps: mixing a boric acid compound and a polymer containing an active hydrogen functional group with a negative electrode slurry, then coating the slurry onto a current collector, and then drying to obtain the negative electrode; (3) The diaphragm is prepared by the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with diaphragm slurry, then coating the slurry onto a polymer porous membrane, and then drying to obtain the diaphragm.
15. The method for preparing a gel electrolyte lithium-ion battery according to claim 14, characterized in that, The drying temperature is 60-120℃.
16. An electrode for a lithium-ion battery, characterized in that, It includes a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer with a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below. , R1 is selected from one of hydroxyl, alkyl, aryl or heteroaryl, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group; When X1, X2, and X3 are each independently selected from O, the groups containing O are selected from: , , or When X1, X2, and X3 are each independently selected from NR2, the group containing NR2 is selected from... ; in, When the O-containing group is selected from At this time, O is directly connected to B, and C is directly connected to the polymer chain; When the O-containing group is selected from At this time, O is directly connected to B, and S is directly connected to the polymer chain; When the group containing NR2 is selected from At this time, N is directly connected to B, and C is directly connected to the polymer chain; At 25-60°C, the polymer with boron cross-linked structure exhibits a swelling degree of 50-10000% in the electrolyte; the swelling loss rate of the polymer with boron cross-linked structure in the electrolyte is <5%. The polymer with a boron crosslinking structure is obtained by reacting a boric acid compound with a polymer containing an active hydrogen functional group; based on 100% of the total weight of the positive electrode slurry, the weight percentage of the sum of the weights of the boric acid compound and the polymer containing an active hydrogen functional group is 1-10%; or, based on 100% of the total weight of the negative electrode slurry, the weight percentage of the sum of the weights of the boric acid compound and the polymer containing an active hydrogen functional group is 1-10%.
17. The electrode of the lithium-ion battery according to claim 16, characterized in that, It includes a current collector and an electrode material coated on the current collector, wherein the electrode material contains a polymer with a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below. , R1 is a phenyl group, and X1, X2, and X3 are each independently selected from O and NR2, where R2 is a hydrogen atom or an alkyl group.
18. The electrode of the lithium-ion battery according to claim 16 or 17, characterized in that, The electrode is either a positive electrode or a negative electrode.
19. A method for preparing an electrode for a lithium-ion battery according to any one of claims 16-18, characterized in that, The lithium-ion battery electrode is prepared by the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with electrode slurry, and then coating and drying the mixture to obtain the electrode.
20. The method for preparing the electrode of the lithium-ion battery according to claim 19, characterized in that, The drying temperature is 60-120℃.
21. A separator for a lithium-ion battery, characterized in that, It includes a polymer porous membrane and a membrane coating material coated on the polymer porous membrane, wherein the membrane coating material contains a polymer with a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of the following formulas 1, 2, 3 and 4. R1 is selected from one of hydroxyl, alkyl, aryl or heteroaryl, and X1, X2 and X3 are each independently selected from one of O and NR2, wherein R2 is a hydrogen atom or an alkyl group; When X1, X2, and X3 are each independently selected from O, the groups containing O are selected from: , , or , When X1, X2, and X3 are each independently selected from NR2, the group containing NR2 is selected from... ; in, When the O-containing group is selected from At this time, O is directly connected to B, and C is directly connected to the polymer chain; When the O-containing group is selected from At this time, O is directly connected to B, and S is directly connected to the polymer chain; When the group containing NR2 is selected from At this time, N is directly connected to B, and C is directly connected to the polymer chain; At 25-60°C, the polymer with boron cross-linked structure exhibits a swelling degree of 50-10000% in the electrolyte; the swelling loss rate of the polymer with boron cross-linked structure in the electrolyte is <5%. The polymer with boron crosslinking structure is obtained by reacting boric acid compounds with polymers containing active hydrogen functional groups; based on the total weight of the diaphragm slurry as 100%, the weight percentage of the sum of the weights of the boric acid compounds and the polymers containing active hydrogen functional groups is 1-50%.
22. The separator for a lithium-ion battery according to claim 21, characterized in that, It includes a polymer porous membrane and a membrane coating material coated on the polymer porous membrane, wherein the membrane coating material contains a polymer with a boron crosslinking structure, and the boron crosslinking structure of the polymer is one or more of Formulas 1, 2, 3 and 4 below. , R1 is a phenyl group, and X1, X2, and X3 are each independently selected from O and NR2, where R2 is a hydrogen atom or an alkyl group.
23. The separator for a lithium-ion battery according to claim 21 or 22, characterized in that, The polymer porous membrane is a polyolefin microporous membrane or a nonwoven fabric.
24. The method for preparing the separator of a lithium-ion battery according to any one of claims 21-23, characterized in that, The process includes the following steps: mixing boric acid compounds and polymers containing active hydrogen functional groups with a membrane slurry, coating and drying to obtain the membrane for the lithium-ion battery.
25. The method for preparing the separator of a lithium-ion battery according to claim 24, characterized in that, The drying temperature is 60-120℃.
Citation Information
Patent Citations
Sodium ion bifunctional gel polymer electrolyte, and preparation method and application thereof
CN113851710A
Sulfur battery
JP2010192385A
